Chemical activation of self-passivating metals
By exposing the stainless steel workpiece to the vapor generated by the heated non-polymerized N/C/H compound, the problem of low-temperature surface hardening of stainless steel workpieces with bisphenol layers without forming carbide precipitates is solved, and the problem of low-temperature surface hardening of stainless steel workpieces with bisphenol layers is achieved. Fast and effective surface hardening.
Patent Information
- Application Number
- CN202080076299.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-10
- Filing Date
- 2020-12-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-12-04
AI Technical Summary
The prior art is difficult to perform low-temperature surface hardening of stainless steel workpieces with ptery layers without forming carbide precipitates, especially on workpieces with complex shapes.
The workpiece is activated for low temperature gap surface hardening by exposing the workpiece to vapor generated by the heated nonpolymerized N/C/H compound. The method includes the use of a reagent having a guanidine moiety and complexing with HCl, or other nonpolymeric N/C/H compounds to produce a reactive vapor.
This method can complete surface hardening in a much shorter time than the conventional method, for example, achieving a comparable hardening effect in 2 hours or less without compromising the corrosion resistance of the workpiece.
Smart Images

Figure CN114929924B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to the following U.S. Provisional Applications: Serial No. 62 / 922,241, filed December 6, 2019; Serial No. 63 / 017,259, filed April 29, 2020; Serial No. 63 / 017,262, filed April 29, 2020; Serial No. 63 / 017,265, filed April 29, 2020; Serial No. 63 / 017,271, filed April 29, 2020, and Serial No. 63 / 076,425, filed September 10, 2020. The entire disclosure of each of these applications is incorporated herein by reference, and priority to each of these applications is hereby claimed. Background Art
[0003] Conventional carburizing
[0004] Conventional (high temperature) carburizing is a widely used industrial process for increasing the surface hardness ("case hardening") of formed metal articles. In the commercial process, a workpiece may be contacted with a carbon-containing gas at high temperatures (e.g., 1,000°C or higher), whereby carbon atoms liberated by decomposition of the gas diffuse into the surface of the workpiece. Hardening occurs by reaction of these diffused carbon atoms with one or more metals in the workpiece to form different chemical compounds, i.e., carbides, which are then precipitated as discrete, extremely hard, crystalline particles in a metal matrix forming the surface of the workpiece. See Stickels, "Gas Carburizing", pp. 312-324, Vol. 4, ASM Handbook, 1991, ASM International.
[0005] Stainless steel is corrosion resistant because the steel forms a chromium oxide surface coating immediately upon exposure to air that blocks water vapor, oxygen, and other chemicals from passing through. Nickel-based, cobalt-based, manganese-based, and other alloys containing large amounts of chromium (which can be 10 weight percent or more) also form these impermeable chromium oxide coatings. Titanium-based alloys exhibit a similar phenomenon in that they also form a titanium dioxide coating immediately upon exposure to air that also blocks water vapor, oxygen, and other chemicals from passing through.
[0006] These alloys are said to be self-passivating not only because they form oxide surface coatings immediately upon exposure to air, but also because these oxide coatings block the permeation of water vapor, oxygen, and other chemicals. These coatings are fundamentally different from the iron oxide coatings (e.g., rust) that iron and other low alloy steels form upon exposure to air. This is because these iron oxide coatings do not block the permeation of water vapor, oxygen, and other chemicals, as can be understood from the fact that if these alloys are not properly protected, they will be completely consumed by rust.
[0007] When stainless steel is conventionally carburized, the chromium content of the steel is locally reduced by forming carbide precipitates which are responsible for the case hardening. As a result, there is not enough chromium in the near-surface region immediately surrounding the chromium carbide precipitates to form protective chromium oxide on the surface. Stainless steel is rarely case hardened by conventional (high temperature) carburizing because the corrosion resistance of the steel is compromised.
[0008] Low temperature carburizing
[0009] In the mid-1980s, a technique for surface hardening of stainless steel was developed, in which the workpiece was contacted with a carbon-containing gas at low temperatures (e.g., less than about 500°C). At these temperatures, and as long as carburizing does not last too long, the carbon atoms released by gas decomposition can diffuse into the workpiece surface, and the depth can reach 20-50 μm without forming carbide precipitates. Nevertheless, a very hard surface layer (surface layer) is obtained. Since carbide precipitates will not be produced, the corrosion resistance of the steel will not be impaired and may even be improved. This technique, which is referred to as "low temperature carburizing", is described in many publications including US5,556,483, US5,593,510, US5,792,282, US6,165,597, EPO 0787817, Japan 9-14019 (Kokai 9-268364) and Japan 9-71853 (Kokai 9-71853).
[0010] Nitriding and carbonitriding
[0011] In addition to carburizing, nitriding and carbonitriding can also be used to case harden various metals. Nitriding works in much the same way as carburizing, except that nitriding uses a nitrogen-containing gas that decomposes to produce nitrogen atoms for case hardening, rather than a carbon-containing gas that decomposes to produce carbon atoms for case hardening.
[0012] However, in the same manner as carburizing, if nitriding is done at higher temperatures and without rapid quenching, hardening occurs by the formation and precipitation of discrete compounds of the diffused atoms (i.e., nitrides). On the other hand, if nitriding is done at low temperatures without a plasma, hardening occurs by the stresses exerted on the crystal lattice by the nitrogen atoms that have diffused into the metal, without the formation of these precipitates. As with carburizing, stainless steels are not usually nitrided by conventional (high temperature) or plasma nitriding processes because the inherent corrosion resistance of the steel is lost when the chromium in the steel reacts with the diffused nitrogen atoms to cause the formation of nitrides.
[0013] In carbonitriding, the workpiece is exposed to nitrogen- and carbon-containing gases simultaneously, whereby both nitrogen atoms and carbon atoms diffuse into the workpiece for case hardening. In the same manner as carburizing and nitriding, carbonitriding can be accomplished at higher temperatures, in which case case hardening occurs by forming nitride and carbide precipitates, or carbonitriding can be accomplished at lower temperatures, in which case case hardening occurs by the sharp local stress fields generated in the crystal lattice by nitrogen and carbon atoms dissolved interstitially in the metal, which have diffused into the lattice. For convenience, all three processes (i.e., carburizing, nitriding, and carbonitriding) are collectively referred to in this disclosure as "low temperature case hardening" or "low temperature case hardening processes."
[0014] activation
[0015] Because of the relatively low temperatures involved in low temperature case hardening, carbon and / or nitrogen atoms will not penetrate the protective chromium oxide coating of stainless steel. Therefore, low temperature case hardening of these metals is usually preceded by an activation ("depassivation") step in which the workpiece is contacted with a halogen-containing gas (such as HF, HCl, NF3, F2, or Cl2) at high temperatures (e.g., 200°C to 400°C) to make the protective oxide coating of the steel permeable to carbon and / or nitrogen atoms.
[0016] WO 2006 / 136166 (US 8,784,576) to Somers et al., the disclosure of which is incorporated herein by reference, describes an improved process for low temperature carburization of stainless steel, wherein acetylene is used as the active ingredient in the carburizing gas, i.e., as a source compound for supplying carbon atoms to the carburizing process. As shown therein, since the acetylene source compound is also sufficiently reactive to depassivate the steel, a separate activation step with a halogen-containing gas is not necessary. Therefore, the carburizing technique of the present disclosure can be considered to be self-activating.
[0017] WO 2011 / 009463 (US 8,845,823) to Christiansen et al., whose disclosure is also incorporated herein by reference, describes a similarly improved process for carbonitriding of stainless steel, wherein oxygen-containing "N / C compounds" such as urea, formamide, etc. are used as source compounds for supplying the nitrogen and carbon atoms required for the carbonitriding process. The disclosed technique can also be considered self-activating, as a separate activation step with a halogen-containing gas is said to be necessary.
[0018] Surface preparation and Bielbay coating
[0019] Low temperature surface hardening is usually carried out on workpieces with complex shapes. In order to form these shapes, some type of metal forming operation is usually required, such as a cutting step (e.g., sawing, scraping, machining) and / or a forging process step (e.g., forging, drawing, bending, etc.). Due to these steps, structural defects of the crystal structure and contaminants such as lubricants, moisture, oxygen, etc. are often introduced into the near-surface area of the metal. Therefore, in most workpieces with complex shapes, a highly defective surface layer is usually produced, which has an ultrafine grain structure caused by plastic deformation and a significant level of contamination. This layer, which can be up to 2.5 μm thick and is called the Bielbai layer, is formed directly below the protective, coherent chromium oxide layer or other passivation layer of stainless steel and other self-passivating metals.
[0020] As mentioned above, the traditional method used to activate stainless steel for low temperature surface hardening is by contact with a halogen-containing gas. These activation techniques are essentially unaffected by this Bieber layer.
[0021] However, the same cannot be said for the self-activation techniques described in the above-mentioned Somers et al. and Christiansen et al. disclosures in which the workpiece is activated by contact with acetylene or "N / C compounds". Rather, experience has shown that if stainless steel workpieces having complex shapes are not surface treated to remove their Bieber layer by electropolishing, mechanical polishing, chemical etching, etc. before surface hardening begins, the self-activating surface hardening techniques of these disclosures do not work at all, or if they do work at all, the results produced are spotty at best and inconsistent between surface areas.
[0022] See Ge et al., The Effect of Surface Finish on Low-Temperature Acetylene-Based Carburization of 316L Austenitic Stainless Steel, METALLURGICAL ANDMATERIALS TRANSACTIONS B, Vol. 458, December 2014, pp. 2338-2345, 2104 The Minerals, Metals & Materials Society and ASM International. As stated therein, "[stainless] steel samples with inadequate surface finish due to, for example, machining could not be successfully carburized by an acetylene-based process." In particular, see FIG. 10(a) and the related discussion on pages 2339 and 2343, which clearly show that a "machining-induced distribution layer" (i.e., a Bielbay layer) that has been intentionally introduced by etching and then scraping with a sharp blade cannot be activated and carburized with acetylene, even though the surrounding portions of the workpiece that have been etched but not scratched will be readily activated and carburized. Therefore, in practice, these self-activating surface hardening techniques cannot be used for stainless steel workpieces with complex shapes unless these workpieces are first pretreated to remove their Bielbay layer.
[0023] To address this problem, commonly assigned US Pat. No. 10,214,805 discloses an improved process for low-temperature nitriding or carbonitriding of workpieces made of self-passivating metals, wherein the workpieces are contacted with vapors generated by heating an oxygen-free nitrogen halide salt. As described, in addition to supplying the nitrogen atoms and optionally carbon atoms required for nitriding and carbonitriding, these vapors are also capable of activating the surfaces of the workpieces for these low-temperature surface hardening processes, even if these surfaces may be provided with a Bieber layer as a result of previous metal forming operations. Thus, this self-activating surface hardening technique can be directly applied to these workpieces, even if these surfaces define complex shapes as a result of previous metal forming operations and even if these surfaces have not been pretreated to remove their Bieber layer.
[0024] Kinetics of Low Temperature Carburization
[0025] Once the workpiece is ready for carburizing, it is contacted with the carburizing gas at high temperature for a time sufficient to diffuse the carbon atoms into the workpiece surface.
[0026] In low temperature carburizing, the carburizing gas is maintained at an elevated carburizing temperature, which is high enough to promote diffusion of carbon atoms into the surface of the article but not so high that carbide precipitates form to any appreciable extent.
[0027] refer to Figure 1 This can be understood more easily by Figure 1 is a time-temperature-transformation (TTT) phase diagram for AISI 316 stainless steel [316SS (UNS S31600)] showing the time and temperature conditions under which carbide precipitates form when the steel is carburized using a specific carburizing gas. In particular, Figure 1 It is shown that, for example, metal carbides of the formula M23C6 will form if the workpiece is heated within the envelope defined by curve A. Therefore, it can be understood that if the workpiece is heated under any time and temperature conditions above the lower half of curve A, carbide precipitates will form in the surface of the workpiece. Therefore, low temperature carburizing is performed below curve A so that carbide precipitates will not form.
[0028] from Figure 1 It can also be seen that for a given carburizing gas, the carburizing temperature that promotes the formation of carbide precipitates varies with carburizing time. For example, Figure 1 It is shown that at a carburizing temperature of 1350°F., carbide precipitates begin to form after only one-tenth of an hour (6 minutes). On the other hand, at a carburizing temperature of about 975°F., carbide precipitates do not begin to form until carburizing has been carried out for about 100 hours. Because of this phenomenon, low temperature carburizing is usually carried out at a constant carburizing temperature that is maintained below the carbide precipitate formation temperature at the end of carburizing. For example, for a carburizing temperature of 1350°F., carbide precipitates are formed after only one-tenth of an hour (6 minutes). On the other hand, at a carburizing temperature of about 975°F., carbide precipitates do not begin to form until carburizing has been carried out for about 100 hours. Because of this phenomenon, low temperature carburizing is usually carried out at a constant carburizing temperature that is maintained below the carbide precipitate formation temperature at the end of carburizing. Figure 1 For low temperature carburizing processes where the alloy and carburizing gas are expected to last 100 hours, carburizing is usually carried out at a constant temperature of 925°F. or lower, as this will safely maintain the workpiece below the temperature at which carbide precipitates form at the end of carburizing (i.e., 975°F). Figure 1 As shown, carburizing will usually be carried out along line M, as this keeps the workpiece safely below point Q, so that no carbide precipitates will form.
[0029] Low temperature carburizing processes may require 50 to 100 to 1000 hours or more to achieve the desired carburizing amount. It will therefore be appreciated that when carburizing is safely carried out at a constant temperature below point Q, the carburizing temperature at any instant in time t during the early stages of carburizing will be well below curve A. This is also Figure 1, where line segment S represents the difference between the temperature of curve A and the carburizing temperature (925°F.) at the end of carburizing, and line segment T represents this difference one hour after the start of carburizing. By comparing line segment S and line segment T, it can be seen that when the carburizing temperature is maintained at a constant 925°F., so that it is at least 50°F. below the Q point at the end of carburizing, then the difference between the actual carburizing temperature and curve A one hour after the start of carburizing will be 150°F. (1175°F.-925°F.). Since the carburizing rate depends on temperature, it can be seen that the relatively low carburizing temperature of 925°F. during the early stages of carburizing slows down the entire carburizing process performed in this manner.
[0030] Adjustment of carburizing temperature
[0031] As discussed in U.S. Pat. No. 6,547,888, this limitation can be largely eliminated by starting the carburizing process at a higher carburizing temperature than has been typically used in the past, and then reducing this temperature as carburizing proceeds to safely reach a carburizing temperature below the envelope defined by the curve in the workpiece phase diagram at the end of the carburizing process.
[0032] Figure 2 Curve X in Figure 1 shows this approach, 1 The curve X is similar to Figure 1 The difference is that curve X shows that the carburizing temperature is reduced from an initial high value to a lower final value during the carburizing process. In particular, curve X shows that carburizing begins at an initial carburizing temperature of 1125°F., which is higher than the temperature at which carbide precipitates begin to form after half an hour of the carburizing process ( Figure 2 The carburizing temperature is then reduced as carburizing progresses to reach a final carburizing temperature of 925°F. at the end of carburizing, which is approximately 50°F. Figure 1 The endpoint temperatures used in the conventional processes shown are the same.
[0033] The carburizing temperature at any time t during the carburizing process is maintained within a predetermined amount (e.g., 50°F., 75°F., 100°F., 150°F., or even 200°F) of the temperature at which carbides begin to form. In other words, the carburizing temperature is maintained below the predetermined temperature amount (e.g., temperature buffer) of Curve A throughout the carburizing process. In this way, the carburizing temperature is maintained at a much higher temperature than in conventional single low temperature operations, but below the temperature at which carbide precipitates begin to form. The net effect of this method is to increase the total carburizing rate because in most carburizing processes, the carburizing temperature is higher than otherwise. At any time t during the carburizing process, the instantaneous rate of carburizing depends on the temperature, and in this method, this instantaneous rate is increased by increasing the instantaneous carburizing temperature. The net effect is a higher total carburizing rate, which in turn makes the total amount of time to complete the carburizing process shorter.
[0034] Of course, when operating at higher carburizing temperatures as described above, it is still necessary to ensure that carbide precipitates are not formed to any substantial extent during the carburizing process. Therefore, as described above, the carburizing temperature is not only set so that at no time t falls below a minimum predetermined amount, but is also set so that it does not exceed a maximum value that is too close to curve A. In other words, the carburizing
[0035] The temperature must remain below curve A by a sufficient amount (e.g., 25°F. or 50°F.) at any time t to ensure that carbide precipitates are not formed. In practical operation, this means that the carburizing temperature will be set within a range below curve A, with its maximum value being a sufficient distance below curve A (e.g., 25°F. or 50°F.) and its minimum value being further below curve A by a predetermined amount mentioned above (i.e., for example, 50°F., 75°F., 100°F., 150°F., or 200°F.). Therefore, the carburizing temperature can be set to reside within a suitable range below curve A (e.g., 25°F. to 200°F. or 50°F. to 100°F.).
[0036] Figure 3 The curve Y in 2 Another way to proceed similarly to the above is shown, except that the carburizing temperature is reduced stepwise rather than continuously. Incremental reduction may be simpler in many cases, especially from an equipment perspective. Because the carburizing process may take several to many hours, the number of increments may vary from as few as three to five to as many as 10, 15, 20, 25 or even more.
[0037] The need for faster surface treatment
[0038] Hardening by many of the methods described above can be time consuming. Many conventional methods require hours or even days to achieve usable hardness levels and substantial carburized layer depths on the order of tens of microns. Therefore, it would be advantageous to develop a method that achieves the hardening levels and depths of prior art methods in less time and cost. Summary of the invention
[0039] A method for treating a workpiece made of a self-passivating metal and having a Biebery layer is disclosed. The method comprises activating the workpiece for low temperature interstitial surface hardening by exposing the workpiece to vapor generated by heating a reagent having a guanidine [HNC(NH2)2] moiety and complexed with HCl.
[0040] A method for producing hardfaced parts in a continuous conveyor belt production is disclosed. The method includes purging the atmosphere of the continuous conveyor belt with a gas while maintaining the atmosphere at a temperature of 600°C or less, placing untreated parts on the continuous conveyor belt, applying a reagent by vapor, solvent, or by carrying the reagent with a carrier, such as coating the untreated parts with a reagent having a guanidine [HNC(NH2)2] moiety and complexed with HCl to activate the parts, exposing the workpiece to vapor generated by heating the reagent to activate the workpiece for low temperature gap surface hardening, and low temperature gap surface hardening the parts in a period of less than 2 hours.
[0041] A method for treating a workpiece made of a self-passivating metal and having a Bieber layer is disclosed. The method comprises exposing the workpiece to a vapor produced by heating one or more non-polymeric N / C / H compounds to activate the workpiece for low temperature interstitial surface hardening at an exposure temperature below the temperature at which nitride and / or carbide precipitates are formed in the workpiece. The one or more N / C / H compounds: (a) are solid or liquid at 25°C and atmospheric pressure, (b) have a molecular weight of ≤5,000 Daltons, and (c) can be uncomplexed or complexed with a hydrohalogen acid. If the non-polymeric N / C / H compound is uncomplexed, any halogen atom replaces one or more labile hydrogen atoms of the non-polymeric N / C / H compound. If the non-polymeric N / C / H compound is complexed, any halogen atom forms part of the hydrohalide complex acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is the time-temperature-transformation (TTT) phase diagram of AISI 316 stainless steel [316SS (UNS S31600)].
[0043] Figure 2 Shown superimposed on Figure 1Several temperature ramp scenarios on the TTT.
[0044] Figure 3 Shown superimposed on Figure 1 More temperature ramp scenarios on TTT.
[0045] Figure 4 An exemplary disk used in some working examples is shown.
[0046] Figure 5 Shown is a graph of the hardness depth measured by the Vickers test for steel treated with two different reagents DmbgHCl and GuHCl according to Table 1.
[0047] 6(a) is a graph of the Auger depth of a case-hardened stainless steel (316SS (UNS S31600)) disk 1 showing the overlapping carbon and nitrogen concentrations in the surface layer in the presence of dimethylbiguanidine hydrochloride (DmbgHCl).
[0048] FIG. 6( b ) is a graph of the Auger depth of a case-hardened stainless steel (316SS (UNS S31600)) disk 1 showing the overlapping carbon and nitrogen concentrations in the surface layer in the presence of guanidine hydrochloride (GuHCl).
[0049] Figure 7 An exemplary ramp temperature scheme is shown superimposed on the TTT phase diagram for 316SS (UNS S31600).
[0050] Figure 8 Shown superimposed on Figure 7 An exemplary ramp-down temperature scheme on the TTT phase diagram in FIG.
[0051] Fig. 9 An optical image of the surface of a treated 316L stainless steel ferrule is shown. DETAILED DESCRIPTION
[0052] Definitions and terminology
[0053] As mentioned above, the fundamental difference between conventional (high temperature) case hardening and the newer low temperature case hardening process first developed in the mid-1980s is that in conventional (high temperature) case hardening, hardening occurs due to the formation of carbide and / or nitride precipitates on the metal surfaces being hardened. In contrast, in low temperature case hardening, hardening occurs due to stresses exerted on the metal lattice at the metal surfaces by carbon and / or nitrogen atoms that have diffused into these surfaces. Because the carbide and / or nitride precipitates responsible for case hardening in conventional (high temperature) case hardening are not present in stainless steels case hardened by low temperature carburizing, and because low temperature case hardening does not adversely affect the corrosion resistance of stainless steels, the original idea was that case hardening only occurs in low temperature carburizing due to the acute local stress fields generated by interstitially dissolved carbon and / or nitrogen atoms that have diffused into the (austenite) crystal structure of the steel.
[0054] However, more recent and more sophisticated analytical work has shown that when alloys where some or all of the alloy volume consists of a ferrite phase are cryogenically surface hardened, relatively small amounts of previously unknown nitride and / or carbide precipitates of a certain type may form in these ferrite phases. Specifically, recent analytical work has shown that in AISI 400 series stainless steels, which typically exhibit a ferrite phase structure, relatively small amounts of previously unknown nitrides and / or carbides may precipitate when the alloys are cryogenically surface hardened. Similarly, recent analytical work has shown that in duplex stainless steels, which contain both ferrite and austenite phases, relatively small amounts of previously unknown nitrides and / or carbides may precipitate in the ferrite phase of these steels when the duplex stainless steels are cryogenically surface hardened. While the exact nature of these previously unknown, newly discovered nitride and / or carbide precipitates remains unknown, it is known that the chromium content of the ferrite matrix immediately surrounding these "pair equilibrium" precipitates is not reduced. As a result, the corrosion resistance of these stainless steels remains unchanged because the chromium responsible for the corrosion resistance remains evenly distributed throughout the metal.
[0055] Thus, for purposes of this disclosure, it will be understood that when reference is made to a workpiece surface layer that is "substantially free of nitride and / or carbide precipitates" or to a workpiece that is case hardened "without forming nitride and / or carbide precipitates" or to "below a temperature at which nitride and / or carbide precipitates are formed," this reference is to the type of nitrides and / or carbides responsible for case hardening in conventional (high temperature) case hardening processes, said precipitates containing sufficient chromium to cause the metal matrix immediately surrounding these precipitates to lose its corrosion resistance due to the reduction in its chromium content. This reference does not relate to the previously unknown newly discovered nitride and / or carbide precipitates disclosed herein, which may form in small amounts in the ferrite phase of AISI 400 stainless steel, duplex stainless steel and other similar alloys.
[0056] Likewise, it should be understood that for the purposes of this disclosure, "carbonitriding" and "nitrocarburizing" or "nitrocarburization" refer to the same process.
[0057] Additionally, "self-passivating" as used in this disclosure in conjunction with reference to alloys processed by the present invention should be understood to refer to alloy types that, upon exposure to air, rapidly form a protective oxide coating that blocks the passage of water vapor, oxygen, and other chemicals. Thus, metals such as iron and low alloy steels that may form an iron oxide coating upon exposure to air are not considered "self-passivating" within the meaning of this term because these coatings do not block the passage of water vapor, oxygen, and other chemicals.
[0058] alloy
[0059] The present invention can be carried out on any metal or metal alloy that is self-passivating in the sense that it forms a coherent protective chromium-rich oxide layer that blocks the passage of nitrogen and carbon atoms after exposure to air. These metals and alloys are well known and described, for example, in earlier patents for low temperature surface hardening processes, examples of which include US5,792,282, US6,093,303, US6,547,888, EPO 0787817 and Japanese Patent Document 9-14019 (Kokai 9-268364).
[0060] Alloys of particular interest are stainless steels, i.e. steels containing 5 to 50 wt. %, preferably 10 to 40 wt. %, Ni and sufficient chromium to form a protective layer of chromium oxide on the surface when the steel is exposed to air. This includes alloys with about 10% or more chromium. Preferred stainless steels contain 10 to 40 wt. % Ni and 10 to 35 wt. % Cr. More preferred are AISI 300 series steels, such as AISI 301, 303, 304, 309, 310, 316, 316L, 317, 317L, 321, 347, CF8M, CF3M, 254SMO, A286 and AL6XN stainless steels. AISI 400 series stainless steels, and especially alloy 410, alloy 416 and alloy 440C, are also of particular interest.
[0061] Other types of alloys that can be processed by the present invention are nickel-based, cobalt-based, and manganese-based alloys that also contain sufficient chromium (e.g., about 10% or more chromium) to form a coherent protective chromium oxide protective coating when the steel is exposed to air. Examples of such nickel-based alloys include Alloy 600, Alloy 625, Alloy 825, Alloy C-22, Alloy C-276, Alloy 20Cb, and Alloy 718, to name a few. Examples of such cobalt-based alloys include MP35N and Biodur CMM. Examples of such manganese-based alloys include AISI 201, AISI 203EZ, and Biodur 108.
[0062] Yet another type of alloy that can be subjected to the present invention is a titanium-based alloy. As is well known in metallurgy, these alloys, upon exposure to air, form a coherent protective titanium oxide coating that also blocks the passage of nitrogen and carbon atoms. Specific examples of such titanium-based alloys include Grade 2, Grade 4, and Ti 6-4 (Grade 5). In the same manner, alloys based on other self-passivating metals such as zinc, copper, and aluminum can also be activated (depassivated) by the techniques of the present invention.
[0063] The particular phase of the metal processed according to the present invention is not critical in the sense that the present invention may be practiced on metals having any phase structure including, but not limited to, austenite, ferrite, martensite, dual phase metals (e.g., austenite / ferrite), and the like.
[0064] Activation with non-polymeric N / C / H compounds
[0065] According to the present invention, a workpiece made of a self-passivating metal and having a Bielbay layer on at least one surface area thereof is activated (i.e., depassivated) to carry out low-temperature surface hardening by contacting the workpiece with the vapor produced by the reagent of the heating (pyrolysis) containing non-polymeric N / C / H compound. Mixtures of different non-polymeric N / H / C compounds can also be used for this purpose. As further discussed below, in addition to depassivating the workpiece, the non-polymeric N / H / C compound of the present invention can also supply nitrogen and carbon atoms to carry out surface hardening simultaneously, such as carburizing, nitriding and / or carbonitriding of the workpiece. Because the amount and degree of these nitrogen and carbon atoms supplied by different non-polymeric N / C / H compounds are different, the mixture of these compounds can be used to customize specific non-polymeric N / C / H compounds, which are used for specific operating conditions required for simultaneous surface hardening.
[0066] The non-polymeric N / C / H compounds of the present invention can be described as any compound that (a) contains at least one carbon atom, (b) contains at least one nitrogen atom, (c) contains only carbon, nitrogen, hydrogen and optionally halogen atoms, (d) is solid or liquid at room temperature (25° C.) and atmospheric pressure, and (e) has a molecular weight of ≤5,000 Daltons. Non-polymeric N / C / H compounds with a molecular weight of ≤2,000 Daltons, ≤1,000 Daltons or even ≤500 Daltons are included. Non-polymeric N / C / H compounds containing a total of 4-50 C+N atoms, 5-50 C+N atoms, 6-30 C+N atoms, 6-25 C+N atoms, 6-20 C+N atoms, 6-15 C+N atoms and even 6-12 C+N atoms are included.
[0067] Specific classes of non-polymeric N / C / H compounds useful in the present invention include primary amines, secondary amines, tertiary amines, azo compounds, heterocyclic compounds, ammonium compounds, azides and nitriles. Among them, non-polymeric N / C / H compounds containing 4-50 C+N atoms are desired. Non-polymeric N / C / H compounds containing 4-50 C+N atoms, alternating C=N bonds and one or more primary amine groups are included. Examples include melamine, aminobenzimidazole, adenine, benzimidazole, guanidine, biguanide, triguanide, pyrazole, cyanamide, dicyandiamide, imidazole, 2,4-diamino-6-phenyl-1,3,5-triazine (benzoguanamine), 6-methyl-1,3,5-triazine-2,4-diamine (acetoguanamine). 3-amino-5,6-dimethyl-1,2,4-triazine, 3-amino-1,2,4-triazine, 2-(aminomethyl)pyridine, 4-(aminomethyl)pyridine, 2-amino-6-methylpyridine and 1H-1,2,3-triazolo(4,5-b)pyridine, 1,10-phenanthroline, 2,2'-bipyridine and (2-(2-pyridyl)benzimidazole). Specific triguanidines include 1,3-bis(diaminomethylene)guanidine and N-(aminomethyl)pyridine.
[0068] Also included are three triazine isomers and various aromatic primary amines containing 4-50 C+N atoms, such as 4-methylaniline (p-toluidine), 2-methylaniline (o-toluidine), 3-methylaniline (m-toluidine), 2-aminobiphenyl, 3-aminobiphenyl, 4-aminobiphenyl, 1-naphthylamine, 2-naphthylamine, 2-aminoimidazole and 5-aminoimidazole-4-carbonitrile. Also included are aromatic diamines containing 4 to -50 C+N atoms, such as 4,4'-methylene-bis(2-methylaniline), benzidine, 4,4'-diaminodiphenylmethane, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene and 2,3-diaminonaphthalene. Hexamethylenetetramine, benzotriazole and ethylenediamine are also of interest.
[0069] Yet another class of compounds, including some of the above compounds, is a compound that forms a nitrogen-based chelate ligand, i.e., a polydentate ligand containing two or more nitrogen atoms arranged to form independent coordination bonds with a single central metal atom. Compounds that form bidentate chelate ligands of this type are included. Examples include o-phenanthroline, 2,2'-bipyridine, aminobenzimidazole, and guanidine chloride (guanidine chloride is discussed further below).
[0070] Still another type of non-polymeric N / C / H compound included is a compound for producing carbon nitride and / or carbon nitride intermediates described in WO 2016 / 027042, the disclosure of which is incorporated herein in its entirety. The intermediate species may participate in or contribute to the low temperature activation and hardening of the workpiece. Precursors that may include melamine and GuHCl may form various carbon nitride species. These species with the empirical formula C3N4 include stacked layers or sheets one atom thick, the layers being formed of carbon nitride, wherein three carbon atoms are present for every four nitrogen atoms. Solids containing as few as 3 such layers and as many as 1000 or more layers are possible. Although carbon nitride is made in the absence of other elements, doping with other elements is contemplated.
[0071] Yet another inclusive subgroup of the above non-polymeric N / C / H compounds are compounds containing 20 or fewer C+N atoms and at least 2 N atoms.
[0072] In some cases, at least 2 N atoms in these compounds are not primary amines attached to a 6-carbon aromatic ring, either directly or through an intermediate aliphatic moiety. In other words, while one or more N atoms in these particular non-polymeric N / C / H compounds may be primary amines attached to a 6-carbon aromatic ring, at least two N atoms in these compounds should be in different forms, e.g., secondary or tertiary amines or primary amines attached to atoms other than a 6-carbon aromatic ring.
[0073] The N atoms in the non-polymeric N / C / H compounds of this subgroup (i.e., non-polymeric N / C / H compounds containing 20 or fewer C+N atoms and at least 2 N atoms) can be directly linked to each other, such as occurs in an azole moiety, but more typically will be linked to each other via one or more intermediate carbon atoms.
[0074] In this subgroup of non-polymeric N / C / H compounds, compounds containing 15 or less C+N atoms and compounds containing at least 3 N atoms are included. Compounds containing 15 or less C+N atoms and at least 3 N atoms are included.
[0075] This subgroup of non-polymeric N / C / H compounds can be considered to have a relatively high degree of nitrogen substitution. In this context, a relatively high degree of nitrogen substitution will be considered to mean that the N / C atomic ratio of the compound is at least 0.2. Compounds with N / C atomic ratios of 0.33 or more, 0.5 or more, 0.66 or more, 1 or more, 1.33 or more, or even 2 or more are included. Non-polymeric N / C / H compounds with N / C atomic ratios of 0.25-4, 0.3-3, 0.33-2, and even 0.5-1.33 are included.
[0076] Non-polymeric N / C / H compounds of this subgroup containing 10 or fewer C+N atoms are included, especially compounds wherein the N / C atomic ratio is from 0.33 to 2 and even from 0.5 to 1.33.
[0077] Non-polymeric N / C / H compounds of this subgroup comprising 8 or fewer C+N atoms are of particular interest, especially compounds wherein the N / C atomic ratio is from 0.5 to 2 or even from 0.66 to 1.5, especially triguanidinyl agents.
[0078] To achieve this relatively high degree of nitrogen substitution, the non-polymeric N / C / H compounds of this subset may include one or more nitrogen-rich moieties, examples of which include imine moieties [C=NR], cyano moieties [-CN], and azo moieties [RN=NR]. These moieties may be part of a 5- or 6-membered heterocyclic ring containing one or more additional N atoms, such as occurs when the imine moiety forms part of an imidazole or triazine group or when the azole moiety forms part of a triazine or triazole group.
[0079] These moieties may also be independent in the sense that they are not part of a larger heterocyclic group. If this is the case, two or more of these moieties may be linked to each other via an intermediate C and / or N atom, such as occurs, for example, when multiple imine moieties are linked to each other via an intermediate N atom (such as occurs in 1,1-dimethylbiguanidine hydrochloride), or when a cyano group is linked to an imine moiety via an intermediate N atom (such as occurs in 2-cyanoguanidine). Alternatively, they may simply be pendant groups to the rest of the molecule, such as occurs in 5-aminoimidazole-4-carbonitrile, or they may be directly linked to a primary amine, such as occurs in 1,1-dimethylbiguanidine hydrochloride, formamidine hydrochloride, acetamidine hydrochloride, 2-cyanoguanidine, cyanamide, and monocyanoguanidine hydrochloride.
[0080] As mentioned above, if the non-polymeric N / C / H compounds of this subgroup contain one or more primary amines, these primary amines are preferably not attached to carbon atoms of the 6-carbon aromatic ring. Instead, they are preferably attached to other atoms, for example to carbon atoms of the imine moiety [C=NR], such as occurs in 1,1-dimethylbiguanidine hydrochloride, formamidine hydrochloride, acetamidine hydrochloride, 2-cyanoguanidine, cyanamide and monocyanoguanidine hydrochloride. Alternatively, the primary amine may be attached directly or indirectly to a heterocyclic moiety containing at least one, and preferably at least two additional N atoms, such as occurs, for example, in 2-aminobenzimidazole, 2-aminomethylbenzimidazole dihydrochloride, 5-aminoimidazole-4-carbonitrile and 3-amino-1,2,4-triazine.
[0081] In this subgroup of non-polymeric N / C / H compounds containing one or more secondary amines, the secondary amine may be part of a heterocycle containing 0, 1 or 2 additional N atoms. An example of such a compound in which the secondary amine is part of a heterocycle containing no additional N atoms is 1-(4-piperidinyl)-1H-1,2,3-benzotriazole hydrochloride. An example of such a compound in which the heterocycle contains one additional N atom is 2-aminobenzimidazole, 2-aminomethylbenzimidazole dihydrochloride, imidazolium hydrochloride, and 5-aminoimidazole-4-carbonitrile. An example of such a compound in which the secondary amine is part of a heterocycle containing two additional N atoms is benzotriazole. Alternatively, the secondary amine may be attached to a cyano moiety, such as occurs in 2-cyanoguanidine and monocyanoguanidine hydrochloride.
[0082] In this subgroup of non-polymeric N / C / H compounds comprising one or more tertiary amines, the tertiary amine may be part of a heterocycle comprising an additional 1 or 2 N atoms, an example of which is 1-(4-piperidinyl)-1H-1,2,3-benzotriazole hydrochloride.
[0083] In some embodiments of the present invention, the non-polymeric N / C / H compound used will contain only N, C and H atoms. In other words, the particular non-polymeric N / C / H compound used will be halogen-free. In other embodiments of the present invention, the non-polymeric N / C / H compound may contain or be associated or complexed with one or more optional halogen atoms.
[0084] One way this can be done is by including a hydrohalic acid, such as HCl, in the compound in an associated or complexed form. If this is the case, such a non-polymeric N / C / H compound is referred to in this disclosure as "complexed". On the other hand, if the non-polymeric N / C / H compound is not complexed with such an acid, the non-polymeric N / C / H compound is referred to in this disclosure as "uncomplexed". In those cases where neither "complexed" nor "uncomplexed" is used, it will be understood that the term in question refers to both complexed and uncomplexed non-polymeric N / C / H compounds.
[0085] Another way in which optional halogen atoms can be included in the non-polymeric N / C / H compounds of the present invention is by replacing some or all of the labile hydrogen atoms of the compound with halogen atoms (preferably Cl, F, or both). For simplicity of description, this subset of uncomplexed non-polymeric N / C / H compounds containing one or more halogen atoms replacing labile H atoms is referred to herein as "halogen-substituted", while the uncomplexed non-polymeric N / C / H compounds of the present invention that do not contain such halogens are referred to herein as "unsubstituted".
[0086] In those embodiments of the present invention where the non-polymeric N / C / H compounds used contain optional halogen atoms, all non-polymeric N / C / H compounds used may contain optional halogen atoms. In addition, two types of halogen-containing non-polymeric N / C / H compounds may be used, namely complexed non-polymeric N / C / H compounds in which the halogen atoms are part of complexed hydrohalic acids and uncomplexed non-polymeric N / C / H compounds in which the halogen atoms replace labile H atoms.
[0087] As described above, if desired, the non-polymeric N / C / H compounds of the present invention can be complexed with suitable halogen acids such as HCl, etc. (e.g., HF, HBr and HI). In this article, "complexed" will be understood to mean the type of association that occurs when a simple halogen acid such as HCl is combined with a nitrogen-rich organic compound such as 2-aminobenzimidazole. Although HCl may dissociate when both are dissolved in water, 2-aminobenzimidazole will not. In addition, when the water evaporates, the solid obtained is composed of a mixture (e.g., a complex) of these individual compounds on an atomic basis. It is not only composed of a salt in which the Cl- anions from HCl are ionically bound to the N atoms in 2-aminobenzimidazole, but the N atoms become positive ions by absorbing the H+ cations derived from HCl.
[0088] When water evaporates from the aqueous mixture of ammonia and HCl, the H+ cations from the HCl combine with the N atoms from the ammonia to form positively charged ammonium cations. As the water continues to evaporate, the Cl- anions from the HCl form ionic bonds with these positively charged ammonium cations. Thus, a new compound is formed, namely ammonium chloride as a salt. The same thing does not necessarily happen when the non-polymeric N / C / H compounds of the present invention are complexed with HCl or other hydrohalic acids because the nitrogen atoms in these compounds are less likely to form ionic salt bonds due to the specific chemical structures of these compounds.
[0089] For example, non-polymeric N / C / H compounds in which the N atoms are present in the form of secondary or tertiary amines can form complexes with bonding rather than just ionic bonding because the vast majority of these N atoms are less able to absorb H+ cations and become positively charged to the extent necessary to form ionic salt bonds. Therefore, in some embodiments of the present invention, the complexed non-polymeric N / C / H compounds preferably contain at least two nitrogen atoms in the form of secondary and / or tertiary amines.
[0090] Similarly, it also seems clear that non-polymeric N / C / H compounds in which at least one N atom is present in the imine moiety (C=NR) also form complexes, and this is particularly true if the carbon atom of the imine moiety is directly attached to the nitrogen atom, such as occurs in imidazole rings, guanidine and its derivatives and acidic amidine compounds, for example formamidine hydrochloride and acetamide hydrochloride. Thus, in other embodiments, the acid-complexed non-polymeric N / C / H compounds of the present invention preferably contain one, two, three or even four imine moieties (C=NR). Compounds in which the carbon atoms of one or more of these imine moieties are directly attached to the N atom are included.
[0091] According to the present invention, it has been found that, despite the presence of a distinct Bielbay layer, the vapor produced by heating and / or pyrolyzing a reagent comprising a non-polymeric N / C / H compound (complexed with or not complexed with hydrogen halides) to a mist form is easy to activate the surface of the self-passivating metal. In addition, in most cases, these vapors also supply nitrogen and carbon atoms for the simultaneous surface hardening of the workpiece. More surprisingly, it has also been found that the surface hardening performed in this manner can be completed in a much shorter time period than was possible in the past. For example, although an earlier activation process may be required followed by 24-48 hours of low-temperature surface hardening to achieve a suitable situation, the activation process of the present invention and low-temperature surface hardening can achieve a comparable situation in two hours or less or even as low as one minute, regardless of whether the surface hardening and activation occur simultaneously or successively.
[0092] Although not wishing to be bound by any theory, it is believed that the vapor of such non-polymeric N / C / H compound decomposes by heating and / or pyrolysis prior to and / or as a result of contact with the workpiece surface to produce ionic and / or free radical decomposition species effective to activate the workpiece surface. In addition, such decomposition also produces nitrogen and carbon atoms which diffuse into the workpiece surface, thereby surface hardening the workpiece by low temperature carbonitriding.
[0093] It will therefore be appreciated that when non-polymeric N / C / H compounds are used for activation in accordance with the present invention, activation and at least some degree of surface hardening will occur simultaneously, which in most cases may make it unnecessary to include additional nitrogen-containing and / or carbon-containing compounds in the system for enhanced surface hardening processes. However, this is not to say that such additional compounds cannot or should not be included.
[0094] In this regard, it should be understood that the extent to which a workpiece is surface hardened when activated according to the present invention depends on a variety of different factors, including the nature of the particular alloy being treated, the particular non-polymeric N / C / H compound being used, and the temperature at which activation occurs. Generally speaking, activation according to the present invention can occur at temperatures slightly lower than those typically associated with low temperature surface hardening. Activation according to the present invention can also occur at higher temperatures, for example, 600° C. and above. In addition, different alloys may differ from one another in the temperatures at which they are activated and surface hardened. In addition, different non-polymeric N / C / H compounds contain greater or lesser relative amounts of nitrogen and carbon atoms.
[0095] In this case, in some embodiments of the invention, a particular alloy may become fully case hardened while being activated only due to the nitrogen and carbon atoms released by the non-polymeric N / C / H compound. If this is the case, it may not be necessary to enhance the case hardening process by including additional nitrogen-containing and / or carbon-containing compounds in the system for supplying additional nitrogen and / or carbon atoms.
[0096] However, in other embodiments of the present invention, only due to the nitrogen atoms and carbon atoms released by non-polymeric N / C / H compounds during activation, specific alloys may not become completely surface hardened. If this is the case, then additional nitrogen-containing and / or carbon-containing compounds may not be included in the system for supplying additional nitrogen atoms and / or carbon atoms to enhance the surface hardening process. Examples include nitrogen, hydrogen, methane, ethane, ethylene, acetylene, ammonia, methylamine and mixtures thereof. If this is the case, then these additional nitrogen-containing and / or carbon-containing compounds can be supplied to the depassivation (activation) furnace at the beginning of depassivation (activation) or at any time before depassivation (activation) is completed. It should be understood that this additional nitrogen-containing and / or carbon-containing compound may be different from the non-polymeric N / C / H compound for surface hardening, but if necessary, this additional nitrogen-containing and / or carbon-containing compound may also be the same compound.
[0097] In addition or as an alternative to enhanced surface hardening during activation in this manner, enhanced surface hardening can be postponed until activation is completed by supplying additional nitrogen- and / or carbon-containing compounds only after activation is complete. If this is the case, enhanced surface hardening can be performed in the same reactor as used for activation or in a different reactor.
[0098] The amount of non-polymeric N / C / H compound used to activate a particular workpiece also depends on many factors, including the nature of the alloy being activated, the surface area of the workpiece being treated, and the specific non-polymeric N / C / H compound being used. Such amounts can be readily determined by routine experimentation using the following working examples as a guide.
[0099] Furthermore, any of the agents described herein may be used concurrently with the agents disclosed in US Pat. No. 10,214,805.
[0100] Finally, it should be noted that an important feature of the present invention is that its non-polymeric N / C / H compounds are oxygen-free. The reason is to avoid the generation of escaped oxygen atoms when these compounds react, which would otherwise occur if these compounds contained oxygen atoms. As mentioned above, it is believed that the activation according to the present invention occurs due to the ions and / or free radical decomposition species generated when the non-polymeric N / C / H compounds of the present invention decompose. It is believed that any such escaped oxygen atoms will react with these ions and / or free radical decomposition species and thus disable these ions and / or free radical decomposition species. In fact, this explains why the process described in the patent of Christiansen et al. above encounters difficulties when the workpiece being processed has a Bielbai layer, because the N / C compounds actually used therein contain a large amount of oxygen. This problem is avoided according to the present invention because the non-polymeric N / C / H compounds being used are oxygen-free.
[0101] Any suitable form of any reagent described herein can be used with the present disclosure. This includes powders, liquids, gases, and combinations thereof. As used herein, "reagent" includes any substance, including non-polymeric N / C / H compounds or other compounds used for metal activation and / or hardening.
[0102] Low temperature heat curing
[0103] As described above, in addition to activating the surface of the self-passivating metal for low temperature nitriding or carbonitriding, the vapor generated by heating the non-polymeric N / C / H compound of the present invention also supplies nitrogen and carbon atoms, which will achieve at least partial thermal hardening of the workpiece by means of these thermal hardening processes even if no additional reagents are included in the reaction system.
[0104] However, if desired, the rate at which low temperature thermal hardening occurs can be increased by including additional nitrogen-containing and / or carbon-containing reagents in the reaction system, particularly by contacting the workpiece with additional nitrogen-containing compounds that are capable of decomposing to produce nitrogen atoms for nitriding, additional carbon-containing compounds that are capable of decomposing to produce carbon atoms for carburizing, additional compounds containing both carbon atoms and nitrogen atoms that are capable of decomposing to produce both carbon atoms and nitrogen atoms for carbonitriding, or any combination of these compounds.
[0105] These additional nitrogen- and / or carbon-containing compounds can be added to the reaction system at any time. For example, the compounds can be added after activation of the workpiece has been completed or while activation is occurring. Finally, the compounds can also be added before activation begins, although it is believed that low temperature surface hardening will be more effective if the compounds are added simultaneously with and / or after activation.
[0106] Activation and heat hardening can be accomplished according to the present invention in a closed system as described, for example, in commonly assigned US 10,214,805, i.e., in a reaction vessel that is completely sealed to prevent any material from entering or leaving during the entire process of the activation and heat hardening process. In order to ensure that activation and heat hardening are properly performed, it is desirable that a sufficient amount of vapor of the non-polymeric N / C / H compound is in contact with the surface of the workpiece, especially those surface areas with a significant Bielbay layer. Because the non-polymeric N / C / H compound used for activation and heat hardening according to the present invention will generally be a granular solid, a simple method of ensuring that contact is properly completed is to coat or otherwise cover these surfaces with such a granular solid and then seal the reaction vessel before heating of the workpiece and the non-polymeric N / C / H compound begins. The non-polymeric N / C / H compound can also be dissolved or dispersed in a suitable liquid and then coated onto the workpiece.
[0107] These methods are particularly convenient when large production runs containing many small workpieces, such as ferrules and catheter fittings, are being heat hardened simultaneously in the same reaction vessel.
[0108] The present method of activation and heat hardening in a closed system as described above is similar in some respects to the technique disclosed in Bessen US Pat. No. 3,232,797, in which a thin steel strip is coated with a guanidine compound including guanidine chloride and then heated to decompose the guanidine compound and nitride the steel strip. However, in the case where the thin steel strip is being nitrided, there is no self-passivation in the sense of forming a firmly adherent, coherent protective oxide coating that blocks the passage of nitrogen and carbon atoms. Thus, the technique described there has little relevance to the present invention, in which stainless steel and other self-passivating metals that block the passage of nitrogen and carbon atoms by contact with vapors of non-polymeric N / C / H compounds as part of a low temperature heat hardening process are transparent to these atoms.
[0109] Rapid hardening using guanidine hydrochloride reagent
[0110] In accordance with the present disclosure, applicants have determined that a specific reagent class of non-polymeric N / C / H compounds containing a guanidine [HNC(NH2)2] moiety or a functional group complexed with HCl exhibits unexpectedly superior results, including providing suitable activation and simultaneous surface hardening of steel in as little as 1 minute rather than 2-48 hours.
[0111] In particular, the results indicate that at least three reagents belong to this system, 1,1-dimethylbiguanidine hydrochloride (hereinafter referred to as "DmbgHCl"):
[0112]
[0113] and guanidine hydrochloride (hereinafter referred to as "GuHCl"):
[0114]
[0115] and biguanide hydrochloride (BgHCl) successfully induced extremely rapid surface hardening under cryogenic conditions. For example, 8 mg of these agents tested individually were able to achieve a hardened surface depth of 20-24 μm after 2 hours of low temperature (500°C) treatment. As detailed below, this result was much faster than other agents using similar methods. The hardened surface layer was formed on the wall of a cylindrical crucible disk made of 316SS (UNS S31600) stainless steel. An image of an exemplary disk 1 is shown in Figure 4 . The disk has a diameter of about 0.5 cm and a height of about 0.5 cm. The disk was machined from round bar stock using standard metal cutting tools. There was no other apparent surface preparation. The machined surface of disk 1 may have a Bilbaye layer. Testing was performed using a Netzsch Synchronous Thermal Analysis (STA) instrument. 3 Disc 1 was case hardened according to the procedure disclosed in U.S. Patent No. 10,214,805 with the following modifications:
[0116]
[0117]
[0118] Table 1
[0119] As shown in Table 1, the applicant has found that these agents can unexpectedly reduce the exposure treatment time from 2 hours to 1 minute with comparable hardening effect. According to Table 1, the hardness depth curves of steel treated with two different agents DmbgHCl and GuHCl measured by Vickers test are shown in Figure 5 These are for 316SS (UNS S31600) stainless steel crucible disks 1 treated at 500°C for 2 hours according to Table 1. There are two disks 1 treated with each of the reagents DmbgHCl and GuHCl. All samples show an increase in hardness in the surface area (approximately 20 μm skin depth).
[0120] The guanidine [HNC(NH2)2] moiety or the functional group complexed with HCl is a chemical structure common to all of DmbgHCl, GuHCl, and BgHCl. Other tested reagents lacking the guanidine moiety did not show a surface depth of about 20 μm under similar conditions in 2 hours or less.
[0121] Other compounds comprising guanidine and HCl are also suitable, such as biguanidine hydrochloride (BgHCl) and melamine hydrochloride (MeHCl). Other suitable guanidine-containing compounds include triguanidine. 7 More specifically, examples of suitable guanidines, biguanidines, biguanidines and triguanidines include chlorhexidine and chlorhexidine salts, analogs and derivatives, such as chlorhexidine acetate, chlorhexidine gluconate and chlorhexidine hydrochloride, picloxydine, alexidine and polyhexane. Other examples are chlorproguanil hydrochloride, proguanil hydrochloride (currently used as an antimalarial agent), metformin hydrochloride, phenformin and buformin hydrochloride (currently used as an antidiabetic agent).
[0122] Although the results herein discuss the use of compounds containing a guanidine moiety complexed with HCl, these results can also be obtained with reagents containing a guanidine moiety that are not complexed with HCl. Similar results can be achieved with reagents complexed with any hydrohalic acid. Reagents containing a guanidine moiety without HCl complexation can also be mixed with other reagents, such as other reagents with HCl complexation discussed in U.S. Patent No. 10,214,805. An important criterion can be whether the reagent or mixture of reagents has a liquid phase when decomposed within the temperature range of low temperature nitrocarburizing (e.g., 450°C to 500°C). The extent to which the reagent evaporates without decomposing before reaching this temperature range is an important consideration.
[0123] Surface layers with overlapping carbon and nitrogen
[0124] The case-hardened surface layer formed in the above test includes two separate sublayers that are unique to low-temperature nitrocarburizing. The outer sublayer is rich in interstitial nitrogen. The inner sublayer is rich in interstitial carbon. The hardness depth curve shows that after 2 hours of treatment with DmbgHCl and GuHCl, the case depths exhibited by these two layers (e.g., a hardened case depth of 20-24 μm) are similar to the case depths achieved after two days of treatment using the more traditional methods and reagents described in U.S. Patent No. 10,214,805. Applicants have also discovered a way to harden stainless steel by forming a carbon-containing surface layer that includes overlapping nitrogen concentrations. Applicants believe that this overlapping nitrogen and carbon concentration may be due to the formation of fine carbide precipitates that do not exhibit a deleterious effect on the characteristics of coarser-grained precipitates that deplete chromium atoms from the nearby base metal (which in turn would adversely affect the chromium oxide passivation layer). Therefore, the fine precipitates can also protect the corrosion-resistant chromium oxide passivation layer on the stainless steel (e.g., by extracting less than 20% of the chromium from the layer). Under low-temperature interstitial hardening conditions, 8 Under conditions such as those described in U.S. Pat. No. 10,214,805, coarse carbide and nitride precipitates may not form. The temperature may be too low for the substitutional diffusion of chromium and other metal atoms necessary to form coarse carbide precipitation. In fact, as detailed above, avoiding detrimental coarse carbide and nitride precipitates is one of the reasons for hardening under these conditions. Under these same conditions,
[0125] Overlapping concentrations of interstitial nitrogen and carbon are also unlikely. See, e.g., Xiaoting Gu et al., "Numerical Simulations of Carbon and Nitrogen Composition Depth Profiles in Nitrocarburized Austenitic Stainless Steels," Metal and Mater. Transactions A, 45A, (2014), 4268-4279 (hereinafter referred to as "Gu et al."), incorporated herein by reference. Gu et al. summarize the thermodynamics behind the physical separation of interstitial carbon and nitrogen concentrations that occurs during low-temperature nitrocarburizing. See, e.g., Gu et al. at 4268 (Abstract) and 4277. Therefore, Gu et al. strongly advise against overlapping concentrations of interstitial carbon and nitrogen. Ibid. However, Gu et al. leave open the possibility of overlapping nitrogen and carbon concentrations where the elements are not purely in the interstitium, for example, being bound in compounds such as nitride or carbide precipitates.
[0126] Although coarse nitride and carbide precipitates and overlapping interstitial carbon and nitrogen are generally excluded by thermodynamics, applicants have recently unexpectedly discovered overlapping carbon and nitrogen concentrations in the surface hardened layer of stainless steel. Applicants believe that these overlapping concentrations are caused by the formation of fine carbide and / or nitride precipitates.
[0127] Figure 6(a) and 6(b) is a graph of the Auger depth of a case-hardened stainless steel (316SS (UNS S31600)) disk 1 showing the overlapping carbon and nitrogen concentrations in the surface layer in the presence of dimethylbiguanidine hydrochloride (DmbgHCl) and guanidine hydrochloride (GuHCl) reagents, respectively. Figure 6(a) and 6(b) The x-axis shows the depth from the surface in micrometers. This is according to Table 2 below for two 316SS crucible plates 1 treated at 470°C for 5 hours (see Figure 4 ). They show only the nitrogen and carbon results for the area of interest. Figure 6(a) shows that nitrogen is more separated in the shallow part of the hardened case depth (1-2μm from the surface). Carbon is present in greater amounts in the deeper parts. Figure 6(b) shows not only the nitrogen-carbon separation, but also a second carbon peak coexisting with nitrogen near the surface.
[0128] therefore, Figure 6(a) and 6(b) It is shown that there is a significant concentration of carbon near the surface, consistent with nitrogen. Figure 6(a) and 6(b) It is also shown that the surface nitrogen concentration is about 8% to 10% atomic. The carbon concentration is 5% to 7% atomic. Therefore, Figure 6(a) and 6(b) This shows that at least some of the carbon is not interstitial and is more likely to be present in carbide precipitates. Applicants speculate that such precipitates may be fine-grained, since, as mentioned above, coarse-grained precipitates are unexpected under these low temperature conditions. See the discussion of Gu et al. and the aforementioned U.S. Patent No. 10,214,805. Such a surface layer may have a carbon concentration of at least 5 to 15 atomic % and a nitrogen concentration of at least 5 to 15 atomic %.
[0129] To generate Figure 6(a) and 6(b) The samples were case hardened according to the procedure disclosed in U.S. Patent No. 10,214,805 with the following modifications:
[0130]
[0131] Table 2
[0132] As shown in Table 2, the applicant found that these agents can unexpectedly shorten the exposure time from 2 hours to 1 minute with comparable hardening effect. Figure 6(a) and 6(b) The surface concentration of carbon coincides with that of nitrogen and is caused by finely precipitated metal carbides. Figure 6(a) and 6(b) As shown in Table 2, there is other evidence to support this hypothesis. For example, the case hardness of the hardened carbide-rich portion has been measured to be harder than the hardness of the interstitial atomic case hardening alone in the absence of such precipitates. In addition, visual inspection of the hardened case structure prepared according to the present application does not show the typical lath structure with the formation of coarser metal carbides and nitrides. All of these data are consistent with the precipitation of fine metal carbides during the low temperature reagent-induced case hardening process described in Table 2.
[0133] The fine-grained carbides in 316SS are expected to have minimal loss of corrosion resistance compared to the more coarse carbides. One reason is that under the low temperature conditions where the fine carbides form, the migration of chromium is expected to be minimal. This indicates that there is less chromium consumption in the chromium oxide passivation layer, thereby providing corrosion resistance to the stainless steel. All of this is consistent with the relatively small size of fine carbides (e.g., relatively small volume and mass compared to coarse carbides). Due to their small size, fine carbides containing less chromium can be formed compared to coarse-grained precipitates. In addition, it is expected that fine precipitates will not have an adverse effect on the steel properties observed in the case of coarse precipitates. These fine precipitates may exist simultaneously with interstitial element impurities such as interstitial nitrogen. In addition, fine nitride precipitates may be present.
[0134] Remote hardening
[0135] As described in the cited references, rapid case hardening of reagent-activated stainless steel (e.g., 316SS stainless steel (UNS S31600)) can be performed when the reagent, particularly the disclosed guanidine reagent complexed with HCl, and the workpiece are in relatively close proximity (e.g., separated by a distance of 0.1 μm or less). Typically, the reagent is in direct proximity to or even in contact with a portion of the steel during the activation and hardening process. Some process designers even consider this close proximity to be necessary for rapid hardening.
[0136] The processing that needs reagent and workpiece to be in close proximity is difficult to expand in industrial process.For example, it is difficult to use a single reagent to activate and harden multiple workpieces.Approaching limitation makes continuous processing (for example, by conveyor belt) difficult even if not impossible.In addition, due to approaching requirement to limit the number of workpieces that each individual reagent can process (for example, at any given time, one reagent and one workpiece), reagent may not be used effectively.In other words, under such conditions, a larger amount of reagent may be needed to process each individual workpiece.
[0137] It would therefore be advantageous to develop a low temperature hardening process in which the reagent and steel could be separated. Such a process would, among other things, allow industry to scale up and use the reagent more efficiently. In addition, more "remote" hardening could avoid the problems caused by machining with closer reagent / workpiece proximity, including less pitting or disturbance of the workpiece surface caused by proximity or contact with the reagent.
[0138] Applicants have discovered that the disclosed procedures, particularly when using the disclosed guanidine reagents complexed with HCl, can be used to remotely harden steel surfaces. That is, it has been discovered that the same or similar surface hardening effects described herein can be achieved when the target surface for hardening is separated from the activating reagent by a distance of 8 inches (20 cm) or more. Recent results have shown that rapid low temperature reagent activated hardening is just as effective when the reagent and workpiece are separated by these close distances as when they are in close proximity.
[0139] In this work, a hardened surface layer was formed on the wall of a cylindrical crucible disk made of 316SS (UNS S31600) stainless steel. An image of an exemplary disk 1 is provided in Figure 4 . The disk has a diameter of about 0.5 cm and a height of about 0.5 cm. The disk was machined from round bar stock using standard metal cutting tools. There was no other apparent surface preparation. The machined surface of disk 1 may have a Bilbaye layer. Testing was performed using a Netzsch Synchronous Thermal Analysis (STA) instrument. 14
[0140] In these experiments, disk 1 was case hardened according to the procedure disclosed in U.S. Patent No. 10,214,805 with the following modifications:
[0141]
[0142] Table 3
[0143] As shown in Table 3, applicants have discovered that these agents can unexpectedly reduce the exposure treatment time from 2 hours to 1 minute with comparable hardening effects.
[0144] like Figure 4 As shown, the pan 1 has a hole 1a at its top. In the experimental configuration, the hole 1a was subjected to a nitrogen purge at atmospheric pressure. The gas chamber was about 8 inches (20 cm) above the pan 1. Vapors escaping from the reagents in charge of the treatment entered the gas chamber along with the analyzer. As discussed below, applicants believe that the vapors travel at least this distance, i.e., 8 inches (20 cm), to make the target hardening as rapid and effective as when the reagents are placed just adjacent to or in contact with the steel. Applicants have shown that there is 0.5 cm of remote hardening within the crucible pan and lid.
[0145] These results indicate that the 316SS metal surface can be effectively activated and surface hardened by the reagent without direct contact with the reagent and at a distance of 8 inches (20 cm) from the reagent.
[0146] The crucible pan and lid of dish 1 were treated at 500°C for 2-5 hours, showing a 28 to 32 μm surface layer at a surface distance of 0.5 cm from the reagent / treatment. Similar results were obtained for DmbgHCl, BgHCl, and GuHCl reagents. In addition, the applicant found that the vapor produced by the decomposition of the reagents could travel at least 8 inches (20 cm). This surface hardening depth in this time period is comparable to the contact hardening described in U.S. Patent No. 10,214,805 and other references cited herein. Therefore, activation and surface hardening treatments appear to be as effective as they are in close proximity (including direct contact) at these distances.
[0147] Based on this data and related observations, the applicants have concluded that vapors from the decomposition reagents are transported to surfaces that are not in contact with the reagents (e.g., crucible plates and lids) and remotely activate and / or harden these surfaces. The applicants are currently analyzing the composition and properties of this vapor. They have found that its efficacy is directly related to the amount of reagent, for example, when the reaction system is lacking reagent (less reagent is used), less remote activation / hardening is observed.
[0148] In one variation, the reagents and metal catalyst in the above process can be mixed together in powder form to increase reactivity. More specifically, the metal catalyst can include 316SS or other alloy metal powder mixed with the reagents. When the reagents are mixed with the metal catalyst such as 316SS powder in a ceramic crucible, greater reagent activity is observed relative to the reagent alone in the ceramic crucible.
[0149] The above development has considerable economic impact. They mean that reagents can process multiple remote surfaces in parallel (for example, simultaneously), just as if each surface is continuously processed and directly contacted with reagents or closely approached with suitable efficacy. For example, the situation of remote, fast, 1 to 2 hours, and even 1 minute of hardening treatment, can be used for the continuous conveyor belt production of hardened parts. Single reagent (for example, DmbgHCl, GuHCl or BgHCl) can be decomposed at a distance from the workpiece when the workpiece (for example, ferrule) moves on the conveyor belt, thereby effectively processing each of them simultaneously. This will greatly improve the production volume and production speed of workpiece hardening. This will also improve the reagent use efficiency. Compared with the situation of continuously processing each workpiece in a separate reaction vessel, under this large-scale treatment scheme, the reagent required for each workpiece will be less.
[0150] Applicants have noted yet other advantages of this process. Remote hardening as described herein avoids some of the problems that arise from maintaining close proximity of the reagents and the treated surface. In particular, direct exposure to the reagents may cause pitting or other adverse surface effects. Remote activation and hardening have not been observed to cause these problems.
[0151] Reagent azeotrope
[0152] In addition to the above configurations, the reagents may also be combined in various azeotropes. Azeotropes are liquid mixtures that have a constant boiling point and composition throughout the evaporation process. The azeotropic evaporation temperature may be close to or above the boiling point of either of the two liquids in the mixture in pure form. Reagent azeotropes may be used in the context of the present disclosure to advantageously combine reagents to enhance or improve the characteristics of the reagents for activation and hardening.
[0153] For example, melamine can be combined with a guanidine reagent (such as any of the guanidine reagents discussed above) in an azeotrope to facilitate the use of melamine in certain hardening processes. Melamine is a cyclic triguanidine (without HCl complexation) whose chemical properties facilitate rapid activation and hardening of the alloys discussed herein. However, the pure form of melamine may not be convenient for activation and hardening applications. This is because the temperature at which pure melamine evaporates is too low to be conducive to hardening by some of the processes disclosed herein. Mixing melamine with an appropriately selected liquid in an azeotrope can effectively increase the evaporation temperature of melamine. For example, when melamine is mixed with another guanidine-like reagent, the mixture can have a higher azeotrope evaporation temperature. This can make the melamine portion of the mixture more useful for inducing hardening at an appropriate temperature. Guanidine-like reagents that can be used in azeotropes with melamine include biguanidine hydrochloride, dimethylbiguanidine hydrochloride, and guanidine hydrochloride. The weight ratios may vary. Exemplary weight ratios of melamine to guanidine in the azeotrope include 5% to 95%, 10% to 90%, 25% to 75%, or 50% to 50%. Other compounds may also be included in the reagent or azeotrope mixture as desired. For example, the mixture of melamine and guanidine reagents may also include additional reagents, or other compounds that may enhance certain properties of the reagent mixture.
[0154] Although the above discussion of melamine in combination with a guanidine-like agent as an exemplary azeotrope, it should be understood that any suitable combination of agents expressly described or included by reference herein is possible. Melamine can be combined with other agents. In addition, as described above, mixtures of three or more agents are also possible, for example to promote the formation of an azeotrope.
[0155] The method for producing a reagent mixture of an azeotrope can include fusing or melting the reagents together at a temperature lower than the boiling point of the individual reagents. The melting point of the resulting mixture or azeotrope can be lower than the melting point of any one of the mixed reagents when pure. Alternatively, a reagent mixture for such an azeotrope can be produced by suspending two or more reagents in a solvent or a finely distilled petroleum distillate (e.g., paint). The solvent can then be removed to leave a reagent mixture. For example, a method of removing the solvent is to evaporate it on a metal or ceramic surface, thereby leaving a mixture of two dry reagents.
[0156] The above development has considerable economic impact. Rapid 1 to 2 hour surface hardening treatments can be used to produce hardened parts on a continuous conveyor belt under a nitrogen (or other atmosphere) purge. The reagents (e.g., DmbgHCl and GuHCl) can be applied directly by spraying or suspended or mixed in a liquid or solid carrier, which can be applied directly to the workpiece (e.g., ferrule) as it moves on the belt by conventional coating methods (e.g., spraying, dipping or steam). Alternatively, the workpiece can be pretreated with some form of reagent (coated with a water-based or oil-based coating, powder coated, etc.). This will greatly increase the production volume and production speed of hardened parts.
[0157] Tracer
[0158] According to yet another feature of the present invention, the treatment reagents (non-polymeric N / C / H compounds) used in the present invention can be enriched with specific uncommon isotopes of C, N, H and / or other elements to be used as tracer compounds for diagnostic purposes. For example, the non-polymeric N / C / H compounds can be seeded at low concentrations with the same or different non-polymeric N / C / H compounds made from rare isotopes of N, C or H, or with completely different compounds made from such rare isotopes. By sensing these tracers using mass spectrometry or other suitable analytical techniques, quality control of the low temperature surface hardening process of the present invention on a production scale can be easily determined.
[0159] To this end, the treatment reagent may be enriched in at least one of the following halide isotopes: ammonium chloride-(15N), ammonium chloride-(15N, D4), ammonium chloride-(D4), guanidine hydrochloride-(13C), guanidine hydrochloride-(15N3), guanidine hydrochloride-(13C, 15N3), guanidine hydrochloride-(D5) and any isomers thereof. Alternatively or additionally, the treatment reagent may be enriched in at least one of the following non-halide isotopes: adenine-( 15 N2), p-toluidine-(phenyl- 13 C6), melamine-( 13 C3), melamine-(triamine- 15 N3), hexamethylenetetramine-(13C6, 15N4), benzidine-(cyclo-D8), triazine (D3) and melamine-(D6) and any isomers thereof.
[0160] Optional accompanying gas
[0161] In addition to the gases mentioned above, the gaseous atmosphere in which activation is performed according to the present invention may also include one or more other accompanying gases, i.e., gases different from the gaseous compounds mentioned above. For example, this gaseous atmosphere may include an inert gas, such as argon as shown in the following working examples. In addition, other gases that do not adversely affect the activation process of the present invention in any significant manner may also be included, examples of which include, for example, hydrogen, nitrogen, and unsaturated hydrocarbons such as acetylene and ethylene.
[0162] Expose the workpiece to atmospheric oxygen
[0163] In yet another embodiment of the invention, the workpiece is exposed to atmospheric oxygen between activation and case hardening, ie, after activation of the workpiece has been substantially completed but before low temperature case hardening has been substantially completed.
[0164] As mentioned above, the traditional way to activate stainless steel and other self-passivating metals for low temperature carburizing and / or carbonitriding is to contact the workpiece with a halogen-containing gas. In this regard, in some early works in this field as described in the aforementioned US5,556,483, US5,593,510 and US5,792,282, the halogen-containing gas used for activation is limited to corrosive and expensive fluorine-containing gases. This is because when other halogen-containing gases, especially chlorine-containing gases, are used, once the workpiece is exposed to atmospheric oxygen between activation and thermal hardening, it will be repassivated. Therefore, in this early work, only those activated workpieces containing a large amount of fluorine atoms can be exposed to the atmosphere without immediate repassivation.
[0165] In accordance with another feature of the present invention, the compromise between the undesirable corrosion and expense associated with the use of fluorine-based activators and the undesirable need to avoid repassivation when using chlorine-based activators has been broken because it has been found that the activated workpieces produced by the present invention, although free of fluorine atoms, are not susceptible to repassivation when exposed to atmospheric oxygen for 24 hours or more.
[0166] Temperature ramp scheme
[0167] Overview
[0168] Applicants have developed a low temperature hardening method that is effective on a time scale of hours rather than days (compared to the methods shown and discussed above, particularly in Figures 1 to 3 ). Therefore, applicants need to develop new methods of temperature adjustment or ramping during the hardening process to promote these faster hardening processes. In particular, applicants have developed temperature ramping procedures that optimize activation and / or hardening while still avoiding the formation of deleterious precipitates at these unprecedented time scales.
[0169] Development of rapid low temperature hardening
[0170] As discussed above, the results indicate that at least DmbgHCl, GuHCl, and BgHCl have successfully induced extremely rapid surface hardening under cryogenic conditions. Specifically, 8 mg of any of the agents tested alone was able to achieve a hardened surface depth of 20-24 μm after 2 hours of treatment at low temperature (500°C). As is evident from the discussion above, this is much faster than in Figures 1 to 3 The processing discussed in the context of is much faster.
[0171] In these studies, a hardened surface layer was formed on the wall of a cylindrical crucible disk made of 316SS (UNS S31600) stainless steel. An image of an exemplary disk 1 is shown in Figure 4 . The disk has a diameter of about 0.5 cm and a height of about 0.5 cm. The disk was machined from round bar stock using standard metal cutting tools. There was no other apparent surface preparation. The machined surface of disk 1 may have a Bilbaye layer. Testing was performed using a Netzsch Synchronous Thermal Analysis (STA) instrument. 18
[0172] Disc 1 was case hardened according to the procedure disclosed in U.S. Patent No. 10,214,805 with the following modifications:
[0173]
[0174] Table 4
[0175] The guanidine [HNC(NH2)2] moiety or the functional group complexed with HCl is a common chemical structure for DmbgHCl, BgHCl, and GuHCl. Other tested agents lacking the guanidine moiety did not show a skin depth of about 20 μm under similar conditions in 2 hours or less. As shown in Table 4, applicants have found that these agents can unexpectedly reduce the exposure treatment time from 2 hours to 1 minute with comparable hardening effects.
[0176] Examples of suitable guanidines, biguanides, biguanides and triguanides for use in this aspect of the disclosure are 22 Included are chlorhexidine and chlorhexidine salts, analogs and derivatives, such as chlorhexidine acetate, chlorhexidine gluconate and chlorhexidine hydrochloride, chlorpheniramine, biguanidine and polyhexanide. Other suitable examples include chlorproguanil hydrochloride, proguanil hydrochloride (currently used as an antimalarial agent), metformin hydrochloride, phenformin and buformin hydrochloride (currently used as an antidiabetic agent).
[0177] Although the results herein discuss the use of compounds containing a guanidine moiety complexed with HCl, these results can also be obtained with reagents containing a guanidine moiety that are not complexed with HCl. Similar results can be achieved with reagents complexed with any hydrohalic acid. Reagents containing a guanidine moiety without HCl complexation can also be mixed with other reagents, such as other reagents with HCl complexation discussed in U.S. Patent No. 10,214,805. An important criterion can be whether the reagent or mixture of reagents has a liquid phase when decomposed within the temperature range of low temperature nitrocarburizing (e.g., 450°C to 500°C). The extent to which the reagent evaporates without decomposing before reaching this temperature range is an important consideration.
[0178] Temperature treatment during rapid hardening
[0179] Applicants share the goals of the above work, particularly U.S. Pat. No. 6,547,888, for determining a temperature treatment regimen to accelerate or promote low temperature hardening. Since the advances in reagent technology discussed above have accelerated the treatment time from days to hours, Applicants have developed an entirely new regimen. Among other things, their goal is to use a temperature profile to optimize the reagent vapor intensity at critical points during the treatment process.
[0180] Temperature ramp scheme
[0181] Different from the temperature adjustment schemes focused on reducing the temperature to avoid the formation of precipitates in the references cited above, the applicant has developed a temperature ramping scheme. Among other things, one purpose of the ramping is to accelerate the generation of thermal degradation products of reagents (for activation or hardening). In particular, the applicant believes that the activation of the workpiece for nitriding and / or carburizing may be the rate limiting step for hardening. Therefore, before overcoming this rate limiting step and substantial activation, it is not necessary to use higher temperature heating. Prior to this, additional heating can not effectively help hardening. They have developed a heating scheme that starts from a relatively low temperature when the activation process is carried out. Once activation is substantially sufficient to make nitrogen and carbon harden the workpiece, the scheme will provide intensive "pulse" heating steps. This intensive pulse decomposes the reagent and provides carbon and nitrogen for hardening at the appropriate time.
[0182] An exemplary temperature ramping scheme is Figure 7 Shown in. Figure 7 is from U.S. Patent Application Publication No. 2010 / 0116377 Figure 2 Replica of the TTT phase diagram for 316SS (UNS S31600). The new proposed temperature ramp scheme is Figure 7 The region where the precipitate forms in the TTT diagram is marked as 7b. The precipitate region 7b is bounded by the curve QQ. It should be understood that Figure 7The temperature ramp 7a in FIG. 1 only presents an advantageous temperature ramping scenario. Figure 7 The specific temperatures and times shown in and associated with temperature ramp 7a are not meant to be exact or precise. Rather, they are intended to illustrate the physical and chemical changes required by the temperature ramping scheme of the present disclosure.
[0183] like Figure 7 As shown, the initial stage is to heat the reagent at 470°C for 30 minutes. This stage can promote the activation of the workpiece. Subsequently, this initial heating ramps up to 480°C for 15 minutes. Finally, in the last 15 minutes of the first hour of heat treatment, the heating ramps up to 500°C. Ramp-up temperature in this manner provides a "pulse-like" or relatively large heating increase within the first hour of heat treatment at a maximum temperature of 500°C, but the duration is relatively short (e.g., 15 minutes). One of the purposes of the pulse is to provide enough heat for decomposing the reagent to provide nitrogen and carbon for the hardening process after the early heating has fully activated the workpiece. Again, these specific times and temperatures are merely illustrative. They show a pulsed heating scheme that can enhance or increase the ability of the reagent to decompose to activate the workpiece within the first hour of treatment. It should be understood that modifying these specific times and temperatures will still be within the scope of the present disclosure, as long as these or similar results are obtained in a similar manner. Exemplary alternative variations of Scheme 5a are: 500°C for 0.5 hours, 510°C for 0.25 hours, and 530°C for 0.25 hours. More generally, the ramping protocols disclosed herein can vary the temperature from at least 450°C or more to 550°C or less, although even greater temperature ranges are possible. The delta or step change in temperature can be at least 100°C or less.
[0184] Figure 7 The temperature scheme 7a in is a step-by-step scheme. Figure 3 As discussed in the context of , this may be advantageous for practical considerations (e.g., given the limitations of experimental or production heating equipment). However, the stepped form of 7a is intended to be illustrative rather than limiting. It should be understood that the same effects described herein can be achieved with a smooth or partially smooth temperature scheme and still be within the scope of the present disclosure.
[0185] Heating scheme 7a can achieve several goals simultaneously. First, it can provide as much heat as possible to the reagent to promote hardening and / or activation of the surface to be treated. Second, by entering Figure 7 Third, Scheme 7a can be avoided by allowing sufficient time to "preheat" the reagents to obtain a bulk temperature of the reagents sufficient to ramp up to the peak value (e.g., Figure 7Once the peak is reached, slow down the heating ( Figure 7 , 1 hour later). Thus, heating scheme 7a can optimize the intensity of the pulse or surge of vapor from the reagent so that the workpiece is heated at critical points in the process (e.g., Figure 7 As discussed above, such heat treatments can "open up" or activate the workpiece for nitrogen and carbon during the hardening process and / or accelerate the actual hardening by carburizing and / or nitrocarburizing.
[0186] Heating scheme 7a can also or alternatively promote initial loading of interstitial carbon and nitrogen atoms in the workpiece at a lower temperature and then proceed to a higher temperature. This can produce fine carbides disclosed herein without producing coarse carbides (or nitrides). Initial loading is believed to suppress the formation of coarse carbides and nitrides.
[0187] Temperature ramp down scheme
[0188] In addition to the ramp-up heat treatment discussed above, Applicants have developed a temperature ramp-down process for rapid hardening on the order of hours rather than days. The purpose of the ramp-down process is to maintain high temperatures in the workpiece during activation and hardening without precipitating carbides or nitrides. As discussed above, higher temperatures drive the kinetics of both the activation and hardening processes, as well as the decomposition of the reagents.
[0189] An exemplary temperature ramping scheme is Figure 8 Shown in. Figure 8 is with Figure 7 The same TTT graph for 316SS (UNS S31600). The new proposed temperature ramp down scheme is Figure 8 The region where the precipitate forms in the TTT diagram is marked as 7b, which is Figure 7 Likewise, the precipitation zone 7b is bounded by the curve QQ. It should be understood that Figure 8 Scheme 8a in FIG. 1 only proposes a favorable temperature ramp down scheme. Figure 8 The specific temperatures and times shown in and associated with temperature ramp 8a are not meant to be exact or precise. Rather, they are intended to illustrate the physical and chemical changes required by the temperature ramping scheme of the present disclosure.
[0190] Figure 8 The temperature scheme 8a in is a step-by-step scheme. Figure 3As discussed in the context of , this may be advantageous for practical considerations (e.g., limitations of experimental or production heating equipment). However, the stepped form of 8a is intended to be illustrative rather than limiting. It should be understood that the same effects described herein can be achieved with a smooth or partially smooth temperature scheme and still be within the scope of the present disclosure.
[0191] like Figure 8 As shown, the initial stage is to heat the reagents at 500°C for 15 minutes. Subsequently, this initial heating is ramped down to 480°C for 15 minutes. Finally, during the last 30 minutes of the first hour of heat treatment, the heating is ramped down to 470°C. In this way, ramping down the temperature avoids Figure 8 Curve QQ in the TTT diagram of , thereby avoiding precipitation zone 7b. In other words, temperature scheme 8a provides increased heating of reagents and workpieces during activation and hardening while avoiding precipitate formation. This increased heating can advantageously increase the kinetics of reagent decomposition, activation and / or hardening. Again, these specific times and temperatures are merely illustrative. They illustrate a ramp-down heating scheme that may increase the kinetics of decomposition, activation and / or hardening. It should be understood that modifying these specific times and temperatures will still be within the scope of the present disclosure, as long as these or similar results are obtained in a similar manner. An exemplary alternative variant of scheme 6a is: 530°C for 0.25 hours, 510°C for 0.25 hours, and 500°C for 0.5 hours. More generally, the ramp-down scheme disclosed herein can vary the temperature from at least 450°C or higher to 550°C or lower, although a larger temperature range is also possible. The delta or step-like change in temperature can be at least 100°C or less.
[0192] Fast solution for 15-20μm hardened layer in 60 seconds
[0193] In addition to the above, applicants have developed a hardening protocol that produces a 15-20 μm hardened layer within approximately 60 seconds of reagent treatment. Samples were produced from 1 / 16 inch rear ferrules made of 316SS steel. During the hardening process, the samples were exposed to vapors formed by heating the following reagents: biguanide hydrochloride, 1,1-dimethylbiguanide hydrochloride, and GuHCl. Both reagents produced a hardened surface depth of 15-20 μm in the ferrule samples.
[0194] The temperature protocol was as follows. First, the sample was linearly ramped from room temperature to approximately 600°C. The ramp was performed at a rate of 25°C / minute. Once 600°C was reached, the temperature was maintained for 60 seconds while the sample was exposed to the reagent vapor. Subsequently, the sample was cooled to room temperature at a rate of 20°C / minute.
[0195] Fig. 9An optical image of a cross section of the surface of a 316L stainless steel ferrule 910 treated in the manner just described is shown. The scheme produces a relatively uniform hardened shell 920 around the periphery of the ferrule sample. The ASTM G61 cyclic potentiodynamic polarization (CPP) test shows that the treated ferrule 910 is overpassivated at about 900mV, indicating relatively high corrosion resistance. These results indicate that the hardened outer layer includes one or more of a dispersion of fine metal carbide precipitates, a dispersion of fine metal nitride precipitates, coarse metal carbide precipitates suspended in a corrosion resistant solid solution treated metal phase, and coarse metal nitride precipitates suspended in a corrosion resistant solid solution treated metal phase. If the precipitate is not a dispersion or is not suspended in a corrosion resistant solid solution treated metal phase, the CPP test will show a pitting mV value below 900mV.
[0196] Combination of heating solutions
[0197] Although heating schemes 7a and 8a are described above, it should be understood that they can be combined. For example, it may be advantageous to perform the heating pulse of scheme 7a after or before scheme 8a. Other combinations and variations are possible and are all included in the scope of the present disclosure.
[0198] significance
[0199] The above developments have considerable economic impact. Heating schemes 5a and 6a and the variations discussed above can shorten the hardening time to even less than the two hours reported above for the guanidine-based reagents (and others). Hardening times of 1 hour or less are possible. Rapid, 1-2 hour or less surface hardening treatments can be used to produce hardened workpieces on a continuous conveyor belt under a nitrogen (or other atmosphere) purge. The reagents (e.g., DmbgHCl and GuHCl) can be sprayed directly on the workpiece (e.g., ferrules) as the workpiece moves on the conveyor belt. Alternatively, the workpiece can be pretreated with some form of reagent (coated with a water-based or oil-based coating, powder-coated, etc.). This will greatly increase the throughput and production speed of hardened parts.
[0200] According to the invention, the temperature to which the workpiece is subjected during activation and / or hardening should be high enough to achieve activation but not so high as to form nitride and / or carbide precipitations.
[0201] In this regard, it should be fully understood that in a low temperature surface hardening process, if the workpiece is exposed to excessive temperatures, unwanted nitride and / or carbide precipitates will form. In addition, it should be understood that the maximum surface hardening temperature that a workpiece can withstand without forming these nitride and / or carbide precipitates depends on many variables, including the specific type of low temperature surface hardening process being performed (e.g., carburizing, nitriding, or carbonitriding), the specific alloy being surface hardened (e.g., nickel-based alloys and iron-based alloys), and the concentration of nitrogen and / or carbon atoms diffused in the workpiece surface. See, for example, commonly assigned US6,547,888. Therefore, it should also be fully understood that when performing a low temperature surface hardening process, care must be taken to avoid excessive surface hardening temperatures to avoid the formation of nitride and / or carbide precipitates.
[0202] When the activation and / or hardening process of the present invention is carried out in the same manner, care should also be taken to ensure that the temperature to which the workpiece is exposed during the activation process is not so high as to form unwanted nitride and / or carbide precipitates. Generally, this means that the maximum temperature to which the workpiece is exposed during activation and simultaneous and / or subsequent surface hardening should not exceed about 700°C, in some cases 600°C, preferably 500°C, or in other cases even 450°C, depending on the specific alloy being treated. Thus, for example, when activating and surface hardening nickel-based alloys, the maximum treatment temperature can be as high as about 700°C, because these alloys generally do not form nitride and / or carbide precipitates before reaching higher temperatures. On the other hand, when activating and surface hardening iron-based alloys such as stainless steel, the maximum treatment temperature should ideally be limited to about 475°C, preferably 450°C, because these alloys tend to become sensitive to the formation of nitride and / or carbide precipitates at higher temperatures.
[0203] As far as the minimum treatment (i.e. activation and / or hardening) temperature is concerned, there is no practical lower limit, except for the fact that the temperature of both the non-polymeric N / C / H compound and the workpiece itself must be high enough for the workpiece to become activated due to the generated vapor. Typically, this means that the non-polymeric N / C / H compound will be heated to a temperature of ≥100°C, although more preferably the non-polymeric N / C / H compound will be heated to a temperature of ≥150°C, ≥200°C, ≥250°C or even ≥300°C. Activation temperatures of ≥350°C, ≥400°C or even ≥450°C are contemplated.
[0204] According to the present invention, specific alloy becomes activated to carry out low temperature surface hardening and / or surface hardening required time also depends on many factors, including the property of the alloy being activated, the specific non-polymeric N / C / H compound being used and the temperature of activation. Generally speaking, activation and / or hardening can be completed in as short as 1 second to as long as 3 hours. However, alloy can be fully activated in 1 to 150 minutes, 1 to 120 minutes, 1 to 90 minutes, 1 to 75 minutes, 1 to 60 minutes, including 5 to 120 minutes, 10 to 90 minutes, 20 to 75 minutes or even 30 to 60 minutes. Hardening can occur simultaneously with activation or subsequently. In any case, hardening may occur on a similar time scale with activation. Specific alloy becomes fully activated time period spent by process of the present invention and can be determined by case by case. In addition, in those cases where activation and surface hardening occur simultaneously, whether or not additional nitrogen and / or carbon compounds are included in the system for strengthening surface hardening, the shortest time of activation will usually depend on the shortest time required for completing the surface hardening process.
[0205] With respect to pressure, the activation and / or hardening process of the present invention may be carried out at atmospheric pressure, above atmospheric pressure, or below atmospheric pressure including a hard vacuum (i.e., at a total pressure of 1 Torr (133 Pa (Pascals) or less)) and a soft vacuum (i.e., at a total pressure of about 3.5 to 100 Torr (about 500 to about 13,000 Pa (Pascals))).
[0206] More working examples
[0207] In order to more thoroughly describe the present invention, the following working examples are provided.
[0208] Example 1
[0209] A machined workpiece made of an A1-6XN alloy (which is a super austenitic stainless steel characterized by an increased nickel content) is placed in a laboratory reactor together with powdered 2-aminobenzimidazole (as an activating compound) arranged in direct contact with the workpiece. The reactor is purged with dry Ar gas and then heated to 327°C for 60 minutes, after which the reactor is heated to 452°C for 120 minutes.
[0210] After removal from the reactor and cooling to room temperature, the workpiece was inspected and found to have a conformal and uniform outer shell (ie, surface coating) exhibiting a near-surface hardness of 630 HV.
[0211] Example 2
[0212] Example 1 was repeated, except that the activating compound consisted of a mixture of guanidine hydrochloride and 2-aminobenzimidazole in a mass ratio of 0.01 to 0.99. In other words, the amount of guanidine hydrochloride was 1 wt % based on the total amount of non-polymeric N / C / H compound used. In addition, the reactor was heated to 452° C. and maintained for 360 minutes instead of 120 minutes.
[0213] The workpiece was found to exhibit a near-surface hardness of 660 HV.
[0214] Example 3
[0215] Example 2 was repeated, except that the workpiece was made of AISI 316 stainless steel and the activating compound consisted of a mixture of guanidine hydrochloride and 2-aminobenzimidazole. In the first run, the mass ratio of guanidine hydrochloride to 2-aminobenzimidazole was 0.01 to 0.99 (1% by weight of guanidine hydrochloride, based on the total amount of non-polymeric N / C / H compound used), while in the second run, this mass ratio was 0.10 to 0.90 (10% by weight of guanidine hydrochloride, based on the total amount of non-polymeric N / C / H compound used).
[0216] The workpiece produced in the first run exhibited a near-surface hardness of 550 HV, while the workpiece produced in the second run exhibited a near-surface hardness of 1000 HV. In addition, the case-hardened surface of the workpiece produced in the second run exhibited excellent case depth and complete conformality throughout its entire surface compared to the case-hardened surface of the workpiece produced in the first run.
[0217] Example 4
[0218] Example 3 was repeated, except that the activating compound used was a mixture of guanidine hydrochloride and 2-aminobenzimidazole in a mass ratio of 0.50:0.50 (50 wt. % guanidine hydrochloride based on the total amount of non-polymeric N / C / H compounds used).
[0219] The hardened surface or "skin" of the workpiece obtained exhibited a near-surface hardness of 900 HV with almost complete conformality throughout its surface, but with some pitting.
[0220] Implementation
[0221] The following is a non-exhaustive list of exemplary embodiments according to aspects of the present disclosure.
[0222] 1. A method for treating a workpiece made of a self-passivating metal and having a Bielbay layer, the method comprising:
[0223] The workpiece is activated for low temperature interstitial surface hardening by exposing the workpiece to vapor generated by heating a reagent having a guanidine [HNC(NH2)2] moiety and complexed with HCl.
[0224] 2. The method of embodiment 1, wherein exposing the workpiece surface hardens the workpiece in addition to activating the workpiece.
[0225] 3. The method according to any one of embodiments 1 to 2, further comprising:
[0226] maintaining a reaction vessel containing the workpiece at a temperature of 700° C. or less during the exposing process; and
[0227] The workpiece forms a surface layer having a carbon concentration of 5 to 15 atomic % and a nitrogen concentration of 5 to 15 atomic %, but substantially containing no coarse carbide or coarse nitride precipitates.
[0228] 4. The method of embodiment 3, wherein:
[0229] forming the surface layer includes forming fine carbide precipitates in the surface layer; and
[0230] The nitrogen in the surface layer exists mainly as at least one of interstitial nitrogen and fine nitride precipitates.
[0231] 5. The method of embodiment 4, wherein:
[0232] Formation of the fine carbide precipitates does not substantially reduce the corrosion resistance provided by a surface passivation layer in the workpiece; and
[0233] The surface passivation layer includes chromium oxide.
[0234] 6. The method of any one of embodiments 1 to 5, wherein at least one of the following:
[0235] The exposure is carried out for a period of 2 hours or less;
[0236] The exposure is performed for a period of 2 minutes or less;
[0237] maintaining a reaction vessel containing the workpiece at a temperature of 700° C. or less during the exposing process;
[0238] The reagent comprises at least one of dimethylbiguanide hydrochloride, guanidine hydrochloride, biguanide hydrochloride and melamine hydrochloride; and
[0239] The low temperature gap surface hardening occurs simultaneously with the exposing.
[0240] 7. The method according to any one of embodiments 1 to 6, wherein the thickness of the surface hardened layer is less than 30 μm and comprises:
[0241] an outer sublayer rich in interstitial nitrogen; and
[0242] Inner sublayer enriched in interstitial carbon.
[0243] 8. A method as described in Embodiment 7, wherein the thickness of the surface hardened layer is less than 20 μm.
[0244] 9. A method as described in any of embodiments 1 to 8, wherein the low-temperature gap surface hardening includes at least one of carburizing, nitriding and nitrocarburizing.
[0245] 10. The method of any one of embodiments 1 to 9, wherein the reagent comprises at least one of an oxygen-free nitrogen halide salt and a non-polymeric N / C / H compound.
[0246] 11. The method of any one of embodiments 1 to 10, wherein the exposing the workpiece in the reaction vessel occurs with the reagent 8 inches (20 cm) or more away.
[0247] 12. A method for producing a hardened component in a continuous conveyor belt production, the method comprising:
[0248] purging the atmosphere of the continuous conveyor belt with a gas;
[0249] While maintaining the atmosphere at a temperature of 700° C. or less:
[0250] placing unprocessed parts on the continuous conveyor belt;
[0251] exposing the workpiece to vapor generated by heating a reagent having a guanidine [HNC(NH2)2] moiety complexed with HCl; and
[0252] The exposure to the vapor of the reagent is maintained for a period of less than 2 hours, thereby activating and surface hardening the part due to exposure to the vapor.
[0253] 13. The method according to embodiment 12, further comprising:
[0254] While maintaining the atmosphere at a temperature of 700° C. or less:
[0255] placing a plurality of additional unprocessed parts on the continuous conveyor belt;
[0256] exposing the additional components on the continuous conveyor belt to the steam to activate the additional components; and
[0257] The additional component is low temperature surface hardened in a period of less than 2 hours.
[0258] 14. A mixture of a first reagent and a second reagent for activating and / or hardening an alloy, wherein the mixture forms an azeotrope of the first reagent and the second reagent and wherein at least one of the reagents comprises a guanidine-containing reagent.
[0259] 15. The mixture of embodiment 14, wherein the evaporation point of the mixture is lower than the evaporation point of the first reagent.
[0260] 16. The mixture of embodiment 15, wherein at least one of the first agent and the second agent comprises melamine.
[0261] 17. The mixture of embodiment 16, wherein at least one of the first agent and the second agent comprises at least one of biguanidine hydrochloride, dimethylbiguanidine hydrochloride, and guanidine hydrochloride.
[0262] 18. A mixture as described in any one of embodiments 14 to 17, wherein the weight ratio of the first agent to the second agent in the mixture is one of 5% to 95%, 10% to 90%, 25% to 75% and 50% to 50%.
[0263] 19. A mixture according to any one of embodiments 14 to 18, wherein:
[0264] The mixture is formed by fusing or melting the first reagent and the second reagent at a temperature below the boiling point of the first reagent and the boiling point of the second reagent; and
[0265] The mixture also includes petroleum distillates and the petroleum distillates are evaporated, leaving a dry mixture of the first and second reagents.
[0266] 20. The method of any one of embodiments 1 to 13, further comprising:
[0267] A heating scheme is applied during the exposure that ramps from a lower temperature to a higher temperature during the exposure to enhance decomposition of the reagent and / or surface hardening of the workpiece.
[0268] 21. The method of embodiment 20, wherein the lower temperature is about 450°C or higher and the higher temperature is about 550°C or lower.
[0269] 22. The method of embodiment 20, wherein the heating scheme is as follows:
[0270] Maintaining the temperature at approximately 470° C. for approximately 30 minutes;
[0271] ramping the temperature from about 470°C to about 480°C;
[0272] Maintain the temperature at 480°C for approximately 15 minutes;
[0273] ramping the temperature from about 480°C to about 500°C; and
[0274] The temperature was maintained at 500°C for approximately 15 minutes.
[0275] 23. A method as described in embodiment 20, wherein the ramping from a lower temperature to a higher temperature includes pulsing the temperature.
[0276] 24. The method according to embodiment 20, wherein the heating scheme is as follows:
[0277] Maintaining the temperature at approximately 500° C. for approximately 15 minutes;
[0278] ramping the temperature from about 500°C to about 480°C;
[0279] Maintain the temperature at 480°C for approximately 15 minutes;
[0280] ramping the temperature from about 480°C to about 470°C; and
[0281] The temperature was maintained at 470°C for approximately 30 minutes.
[0282] 25. A method for treating a workpiece made of a self-passivating metal and having a Bieberbai layer, the method comprising:
[0283] exposing the workpiece to vapor generated by heating one or more non-polymeric N / C / H compounds to activate the workpiece for low temperature interstitial hardening at an exposure temperature below a temperature at which coarse nitride and / or coarse carbide precipitates are formed in the workpiece, wherein the one or more N / C / H compounds:
[0284] (a) solid or liquid at 25°C and atmospheric pressure;
[0285] (b) a molecular weight of 5,000 Daltons or less; and
[0286] (c) may be uncomplexed or complexed with a hydrohalic acid, and further wherein:
[0287] (i) if the non-polymeric N / C / H compound is uncomplexed, any halogen atom replaces one or more labile hydrogen atoms of the non-polymeric N / C / H compound, and
[0288] (ii) If the non-polymeric N / C / H compound is complexed, any halogen atoms form part of the hydrogen halide complex acid.
[0289] 26. The method of embodiment 25, wherein at least one of the following:
[0290] The exposure temperature is between 500°C and 700°C;
[0291] The molecular weight of the non-polymeric N / C / H compound is ≤ 500 Daltons; and
[0292] The exposure time is 1 hour or less.
[0293] 27. The method of any one of embodiments 25 to 26, wherein the self-passivating metal comprises at least one of:
[0294] Titanium-based alloys;
[0295] An iron-based, nickel-based, cobalt-based or manganese-based alloy containing at least 10 wt.% Cr; and
[0296] Stainless steel containing 10 to 40 wt% Ni and 10 to 35 wt% C.
[0297] 28. The method of any one of embodiments 25 to 27, wherein the exposure temperature is about 600° C. or less.
[0298] 29. The method of any one of embodiments 25 to 28, wherein the exposure temperature is about 550°C or less.
[0299] 30. A workpiece produced according to the method of any one of embodiments 1 to 11 and 20 to 28.
[0300] 31. A workpiece manufactured according to the method of any one of embodiments 12 and 13.
[0301] 32. A workpiece manufactured by using the mixture according to any one of embodiments 14 to 19.
[0302] Although only a few embodiments of the present invention have been described above, it should be appreciated that many modifications may be made without departing from the spirit and scope of the present invention. All such modifications should be included within the spirit and scope of the present invention, which is limited only by the following claims.
Claims
1. A method for treating a workpiece made of a self-passivating metal and having a Bielbay layer, the method comprising: The workpiece is nitrocarburized, wherein the nitrocarburizing consists of exposing the workpiece at a constant pressure to vapor generated by heating a dehydrated reagent having guanidine [HNC(NH2)2] moieties complexed with HCl for a period of 1 minute to 5 minutes.
2. The method according to claim 1, further comprising: maintaining a reaction vessel containing the workpiece at a temperature of 700° C. or less during the exposing process; as well as wherein exposing the workpiece to the vapor forms a treated surface layer in the workpiece, the treated surface layer having a carbon concentration of 5 to 15 atomic % and being substantially free of coarse carbide or coarse nitride precipitates.
3. The method according to claim 2, wherein: The treated surface layer includes fine carbide precipitates; and The nitrogen in the treated surface layer is mainly present as at least one of interstitial nitrogen and fine nitride precipitates.
4. The method according to claim 3, wherein: The fine carbide precipitates do not substantially reduce the corrosion resistance provided by the surface passivation layer in the workpiece; and The surface passivation layer includes chromium oxide.
5. The method of claim 1, wherein at least one of the following: exposing the workpiece to the vapor further comprises maintaining a reaction vessel containing the workpiece at a temperature of 700° C. or less during the exposing; and The reagent includes at least one of dimethylbiguanide hydrochloride, guanidine hydrochloride, biguanide hydrochloride and melamine hydrochloride.
6. The method of claim 1, wherein exposing the workpiece to the vapor further comprises forming a surface hardened layer having a thickness of less than 30 μm and comprising: an outer sublayer rich in interstitial nitrogen; and Inner sublayer enriched in interstitial carbon. The method according to claim 6 , wherein the thickness of the surface hardened layer is less than 20 μm.
8. The method of claim 1, wherein the reagent comprises at least one of an oxygen-free nitrogen halide salt and a non-polymeric N / C / H compound.
9. The method of claim 1, wherein exposing the workpiece to the vapor occurs with the workpiece in a reaction vessel 8 inches (20 cm) or more away from the reagent.
10. A method for hardening the surface of at least one component in the production of a continuous conveyor belt, the method comprising: purging the atmosphere of the continuous conveyor belt with a gas; While maintaining the atmosphere at a temperature of 700° C. or less: placing the at least one component on the continuous conveyor, the at least one component comprising a self-passivating metal and having a Bilbaye layer; The at least one component is nitrocarburized, wherein the nitrocarburizing consists of exposing the at least one component to vapor generated by heating a dehydrated reagent having guanidine [HNC(NH2)2] moieties and complexed with HCl at a constant pressure for a period of 1 minute to 5 minutes, thereby activating and surface hardening the at least one component due to exposure to the vapor. The method of claim 10 , wherein the at least one component comprises a plurality of components.
12. The method of claim 1 , wherein exposing the workpiece to the vapor further comprises: A heating regime is applied that ramps from a lower temperature to a higher temperature during the exposure to enhance decomposition of the reagent and / or surface hardening of the workpiece.
13. The method of claim 12, wherein the lower temperature is about 450°C or higher and the higher temperature is about 550°C or lower.
14. The method of claim 12, wherein the heating scheme is as follows: Maintaining the temperature at approximately 470° C. for approximately 30 minutes; ramping the temperature from about 470°C to about 480°C; Maintain the temperature at 480°C for approximately 15 minutes; ramping the temperature from about 480°C to about 500°C; and The temperature was maintained at 500°C for approximately 15 minutes.
15. The method of claim 12, wherein applying a heating protocol comprises pulsing a lower temperature to a higher temperature.
16. The method of claim 12, wherein the heating scheme is as follows: Maintaining the temperature at approximately 500° C. for approximately 15 minutes; ramping the temperature from about 500°C to about 480°C; Maintain the temperature at 480°C for approximately 15 minutes; ramping the temperature from about 480°C to about 470°C; and The temperature was maintained at 470°C for approximately 30 minutes.
17. A method for treating a workpiece made of a self-passivating metal and having a Bilbaye layer, the method comprising: nitrocarburizing the workpiece, wherein the nitrocarburizing consists of exposing the workpiece at a constant pressure to vapor generated by heating a dehydrated reagent comprising one or more non-polymeric N / C / H compounds for a period of time of 1 minute to 5 minutes, wherein the one or more N / C / H compounds: (a) solid or liquid at 25°C and atmospheric pressure; (b) a molecular weight of 5,000 Daltons or less; and (c) may be uncomplexed or complexed with a hydrohalic acid, and further wherein: (i) if the non-polymeric N / C / H compound is uncomplexed, any halogen atom replaces one or more labile hydrogen atoms of the non-polymeric N / C / H compound, and (ii) If the non-polymeric N / C / H compound is complexed, any halogen atoms form part of a hydrogen halide complex acid.
18. The method of claim 17, wherein at least one of the following: The exposure temperature is between 500°C and 700°C; and The molecular weight of the non-polymeric N / C / H compound is ≤500 Daltons.
19. The method of claim 17, wherein the self-passivating metal comprises at least one of: Titanium-based alloys; An iron-based, nickel-based, cobalt-based or manganese-based alloy containing at least 10 wt.% Cr; and Stainless steel containing 10 to 40 wt% Ni and 10 to 35 wt% C.
20. The method of claim 17, wherein the exposure temperature is about 600°C or less.
21. The method of claim 17, wherein the exposure temperature is about 550°C or less.
22. A workpiece manufactured according to the method of any one of claims 1 to 9.
23. A component manufactured according to the method of any one of claims 10 to 16.
24. A workpiece manufactured according to the method of any one of claims 17 to 21.
Citation Information
Patent Citations
Carbohardened product for joining and its production
JP1997071853A
Enhanced activation of self-passivating metals
US10214805B2
Improvement in puddling-furnaces
US140140A
Integrated transducer data system
US20060136166A1
Hybrid carburization with intermediate rapid quench
US20100116377A1